Analytical carrier and method for manufacturing analytical carrier
Patent Information
- Application Number
- JP2025058507
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0011】 本開示によれば、有機溶媒を含む展開溶媒を用いて分析することが可能な分析用担体、及び分析用担体の製造方法を提供することができる。
Smart Images

Figure 2026165878000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to analytical carriers and methods for manufacturing analytical carriers. [Background technology]
[0002] Immunochromatography is a well-known analytical method for analyzing analytes supported on an analytical carrier. Lateral flow test kits utilizing immunochromatography are also known. These test kits consist of a test strip containing a labeled antibody that reacts with the analyte and is labeled with labeled particles such as gold colloid particles, latex particles, and fluorescent particles, as well as a capture antibody that reacts with the analyte and is immobilized at a predetermined site on the analytical carrier.
[0003] In this test kit, for example, a sample containing the target antigen is collected from a living organism, and a solution containing this sample is dropped onto a designated area in the test kit. The antigen reacts with the labeled antibody to form a complex. The solution containing the complex then flows through the analytical carrier by capillary action. Furthermore, as the solution containing the complex spreads across the analytical carrier, the antigen contained in the complex is captured by the capture antibody on the analytical carrier, and the complex accumulates at the capture site, causing color development. In this way, the degree of color development at the capture site with the complex supported by the analytical carrier is confirmed visually or by measurement, allowing for the determination of whether the sample contains the antigen.
[0004] The test kit, as shown in Patent Document 1, for example, includes a nitrocellulose membrane filter as a test strip for developing the sample. The collected sample flows through the porous portion of the membrane filter with the developing solvent and is developed to the test line and control line. [Prior art documents] [Patent Documents]
[0005]
Patent Document 1
Summary of the Invention
Problem to be Solved by the Invention
[0006] Membranes made of nitrocellulose generally have high whiteness, so that test lines and control lines can be visually confirmed relatively easily, and are used in many test kits.
[0007] However, nitrocellulose membranes have low resistance to organic solvents. For this reason, when a developing solvent containing an organic solvent is used in a test kit using a nitrocellulose membrane filter, the porous portion of the nitrocellulose membrane filter dissolves, the porous structure cannot be maintained, and the wicking performance may be lost.
[0008] The present disclosure has been made in view of the problems of such conventional art. An object of the present disclosure is to provide an analysis carrier that enables analysis using a developing solvent containing an organic solvent, and a method for producing the same.
Means for Solving the Problem
[0009] An analysis carrier according to a first aspect of the present disclosure includes a porous body and a support that supports the porous body on one surface thereof. The porous body includes a skeleton formed by aggregation of a plurality of hollow particles, and a plurality of voids surrounded by the skeleton. The hollow particle has an outer shell including an anodized film containing aluminum oxide, and a cavity surrounded by the outer shell. The skeleton is formed by continuous outer shells of the plurality of hollow particles. The porosity of the porous body is 50% by volume or more and less than 100% by volume. The average pore diameter of the porous body is 0.1 μm or more and 20 μm or less. The support includes an adhesive layer that adheres to the porous body. The adhesive layer is adhered to the outer shell. The support includes a resin or elastomer having organic solvent resistance.
[0010] A method for manufacturing an analytical carrier according to a second aspect of this disclosure comprises a porous body and a support including an adhesive layer that supports the porous body on one surface and adheres to the porous body. The porous body includes a skeleton formed by the aggregation of a plurality of hollow particles and a plurality of voids surrounded by the skeleton. The hollow particles have an outer shell including an anodic oxide film containing aluminum oxide and a cavity surrounded by the outer shell. The skeleton is formed by the continuous arrangement of outer shells of a plurality of hollow particles. The manufacturing method includes a sintering step of sintering a plurality of aluminum metal particles on an aluminum substrate to obtain a sintered material comprising an aluminum substrate and a sintered body laminated on the aluminum substrate and in which the aluminum metal particles have been sintered. The manufacturing method includes an anodizing step of anodizing the sintered material to form an outer shell including an anodic oxide film on the surface of the aluminum metal particles. The manufacturing method includes a dissolving step of dissolving the aluminum metal particles surrounded by the outer shell. In the manufacturing method, a metal member in which a porous body is laminated on an aluminum substrate is formed by performing the anodizing step and the dissolving step once each or by repeating them. The above manufacturing method includes a lamination step of bonding a porous metal component to a support, bonding the adhesive layer to the outer shell, and forming a laminate in which an aluminum substrate, a porous component, and a support are laminated in this order. The above manufacturing method includes a peeling step of dissolving the aluminum substrate and peeling it off from the laminate. The aluminum metal particles contain at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys. The aluminum substrate contains at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys. The average particle size of the multiple aluminum metal particles is 0.1 μm or more and 20 μm or less. The filling density of the sintered body is 10 volume% or more and 60 volume% or less. The support contains a resin or elastomer that is resistant to organic solvents. [Effects of the Invention]
[0011] According to this disclosure, it is possible to provide an analytical carrier that can be analyzed using a developing solvent containing an organic solvent, and a method for producing an analytical carrier. [Brief explanation of the drawing]
[0012] [Figure 1] This is a schematic cross-sectional view showing an example of an analytical carrier according to one embodiment. [Figure 2] This is a perspective view showing an example of a test kit according to one embodiment. [Figure 3] This is a flowchart showing an example of a method for manufacturing an analytical carrier according to one embodiment. [Figure 4] This is a cross-sectional view showing an example of a sintered material obtained by sintering multiple aluminum metal particles on an aluminum substrate. [Figure 5] This is a cross-sectional view showing an example of a state in which a sintered material has been anodized to form an outer shell containing an anodic oxide film on the surface of aluminum metal particles. [Figure 6] This is a cross-sectional view showing an example of aluminum metal particles surrounded by an outer shell in a molten state. [Figure 7] This is a cross-sectional view showing an example of a laminate formed by bonding a porous metal component to a support. [Figure 8] This is a schematic diagram illustrating an example of the first lamination method. [Figure 9] This is a schematic diagram illustrating an example of the second lamination method. [Figure 10] This is a schematic diagram illustrating an example of the third layering method. [Figure 11] This is a schematic diagram illustrating an example of the fourth lamination method. [Figure 12] This is a cross-sectional view showing an example of a state in which the aluminum substrate has been melted and peeled off from the laminate. [Figure 13] This is a schematic plan view showing the state before the bending test is performed. [Figure 14] This is a schematic side view showing the analytical support material in a bent state during a bending test. [Figure 15] This is a schematic side view illustrating the process of conducting a suction test. [Modes for carrying out the invention]
[0013] The analytical carrier, immunochromatography test strip, test kit, and method for manufacturing the analytical carrier according to this embodiment will be described in detail below with reference to the drawings. This disclosure is not limited to the following embodiments. Furthermore, some or all of the components in the embodiments can be combined as appropriate. Note that the dimensional ratios in the drawings are exaggerated for illustrative purposes and may differ from the actual ratios.
[0014] [1. Analytical carriers] First, the analytical carrier 1 according to this embodiment will be described with reference to Figure 1. Figure 1 is a schematic cross-sectional view showing an example of the analytical carrier 1. As shown in Figure 1, the analytical carrier 1 comprises a porous body 10 and a support 20 that supports the porous body 10 on one side. In this case, if the aluminum oxide of the outer shell constituting the porous body 10 and the aluminum oxide on the surface of the aluminum substrate are integrated and supported, when the aluminum substrate undergoes plastic deformation, a fracture may occur between the surface of the aluminum substrate and the outer shell of the porous body, causing the porous body to peel off from the aluminum member. Therefore, in the analytical carrier 1 according to this embodiment, the porous body 10 is supported by the support 20, and the support 20 includes an adhesive layer 22 that adheres to the porous body 10, and the adhesive layer 22 adheres to the outer shell 14, so it has been found that it is possible to suppress the peeling of the porous body 10 from the support 20 even when subjected to bending deformation. The analytical carrier 1 according to this embodiment will be described in detail below.
[0015] <Porous material> The porous body 10 includes a framework 11 and a plurality of voids 12 surrounded by the framework 11. The framework 11 is formed by the aggregation of a plurality of hollow particles 13. The voids 12 are formed by the internal space of the porous body 10 surrounded by the framework 11 or the plurality of hollow particles 13. The hollow particles 13 have an outer shell 14 and a cavity 15 surrounded by the outer shell 14. The framework 11 includes the outer shell 14, and the surface of the framework 11 is formed by the outer shell 14. The framework 11 is formed by the continuous arrangement of the outer shells 14 of the plurality of hollow particles 13. The three-dimensional network structure of the framework 11 is formed by the connection of the hollow particles 13 via the outer shell 14. The outer shell 14 is located on the outer surface side of the porous body 10.
[0016] The outer shell 14 of the hollow particle 13 may have through holes 16 that penetrate the outer shell 14 in the thickness direction. The through holes 16 may connect the inner cavity 15 of the hollow particle 13 separated by the outer shell 14 with the outer void 12 of the hollow particle 13. The through holes 16 may also connect the cavities 15 of adjacent hollow particles 13. The cavities 15 can communicate with the outside of the hollow particle 13 or the skeleton 11 through the through holes 16. When the porous body 10 is impregnated with a liquid containing a sample or the like, the liquid can flow into or out of the cavities 15 from the through holes 16 of the outer shell 14. In addition, the cavities 15 contained in adjacent hollow particles 13 are in communication with each other. Therefore, when the porous body 10 is impregnated with a liquid, the liquid can flow inside the skeleton 11 by passing through the cavities 15 via the through holes 16.
[0017] In immunochromatography, as will be described later, labels such as colored particles, gold colloid particles, or fluorescent beads are typically used. When the analytical carrier 1 is used, for example, as a test strip for immunochromatography, the porous body 10 can absorb the solution in which the label is dispersed by capillary action. The mechanism at which this occurs is not clear, but it is presumed that the solution in which the label is dispersed penetrates the voids 12 and cavities 15 present inside the porous body 10, and that some of it flows along the surface of the porous body 10. Furthermore, although absorption mainly occurs as the solution flows through the voids 12, it is also presumed that the flow of the solution through the cavities 15 and through-holes 16 contributes to absorption.
[0018] In this way, the porous body 10 is a porous body having voids 12 inside that communicate with the outside. In this case, the voids 12 are surrounded by an outer shell 14. That is, the voids 12 are formed surrounded by a skeleton 11 inside the porous body 10 or an outer shell 14 formed on its surface. A void 12 that forms one cell structure surrounded by an outer shell 14 may communicate with voids 12 that form other cell structures. Specifically, the porous body 10 may have an open-cell structure. Also, a single void 12 or multiple voids 12 may or may not penetrate from one surface to the other of the porous body 10.
[0019] The average particle diameter of the multiple hollow particles 13 is 0.1 μm to 20 μm. By setting the average particle diameter to 0.1 μm or more, the strength of the porous body 10 is improved, and damage during transport can be suppressed. By setting the average particle diameter to 20 μm or less, the flow rate of the analytical carrier 1 can be improved. The average particle diameter may be 1 μm or more, 3 μm or more, or 5 μm or more. The average particle diameter may be 18 μm or less, 15 μm or less, or 10 μm or less.
[0020] The average particle diameter of multiple hollow particles 13 can be measured by observing the cross-section of the porous body 10 with a scanning electron microscope. For example, although some aluminum metal particles after sintering are fused together, the parts with a roughly circular shape can be considered approximately circular. Therefore, in the above cross-sectional observation, the maximum diameter (longest axis) of each aluminum metal particle with a roughly circular shape is taken as the particle diameter, and the particle diameters of any 50 aluminum metal particles are measured, and the arithmetic mean of these is taken as the average particle diameter of the aluminum metal particles after sintering. The average particle diameter of multiple aluminum metal particles before sintering is the D50 value obtained by measuring the particle size distribution on a volume basis using the laser diffraction method. Note that within the range of 0.1 μm to 20 μm, almost no secondary particles of aluminum metal particles are formed. Therefore, the average particle diameter of the hollow particles 13 after sintering observed with a scanning electron microscope is almost the same as the average particle diameter of the aluminum metal particles before sintering measured by the laser diffraction method.
[0021] The shape of each hollow particle 13 is not particularly limited and may be spherical, polygonal, irregularly shaped, flaky, or fibrous. Among these, the shape of the hollow particle 13 is preferably spherical. When the shape of the hollow particle 13 is spherical, the size of the multiple voids 12 becomes uniform. For example, in immunochromatography, as will be described later, labels such as colored particles, gold colloid particles, or fluorescent beads are used. When the size of the voids 12 is uniform, such labels are not trapped in the voids 12 and can flow smoothly through the porous body 10. Note that the term "spherical" here does not mean a perfect sphere, but may also mean having some irregularities on the surface. Furthermore, the term "spherical" here does not mean only those with an aspect ratio of 1, but may also include hollow particles 13 with an aspect ratio of 1 or more. The aspect ratio of the hollow particle 13 may be 5 or less, 3 or less, or 2 or less. Note that the aspect ratio is the ratio of the major axis to the minor axis of the hollow particle 13, and is the average value of multiple hollow particles 13.
[0022] The outer shell 14 contains an anodic oxide film containing aluminum oxide. The anodic oxide film contained in the outer shell 14 may be a barrier-type anodic oxide film or a porous-type anodic oxide film. The outer shell 14 may be formed solely by a barrier-type anodic oxide film, or it may be formed by a two-layer anodic oxide film in which a porous-type anodic oxide film is formed on the outside of a barrier-type anodic oxide film. The outer shell 14 may have a hydration film containing aluminum hydroxide. The hydration film is formed in a hydration treatment process described later.
[0023] The ratio of metallic aluminum to the components constituting the porous body 10, which contains aluminum elements, may be 0 or more and 0.1 or less by mass ratio. In other words, the ratio of the mass of metallic aluminum contained in the porous body 10 to the mass of the components constituting the porous body 10, which contains aluminum elements, may be 0 or more and 0.1 or less by mass ratio. The mass of the components constituting the porous body 10, which contains aluminum elements, refers to the total mass of aluminum oxide, aluminum hydroxide, electrolyte anions, resin residue (burnt residue), and metallic aluminum contained in the porous body 10. By setting the ratio of metallic aluminum to 0.1 or less, the light transmittance of the porous body 10 is increased even when the porous body 10 has absorbed water, thereby reducing the gray color caused by the aluminum metal. This improves the discriminability when water is absorbed. The ratio of metallic aluminum is preferably 0.05 or less, more preferably 0.01 or less, and even more preferably 0.001 or less. The ratio of metallic aluminum to the components constituting the porous body 10, which contains aluminum elements, can be calculated based on JIS G2404:2022. The outer shell 14 of the hollow particles 13 may consist solely of an anodic oxide film substantially containing aluminum oxide.
[0024] The thickness of the outer shell 14 is preferably 40 nm to 1000 nm. By setting the thickness of the outer shell 14 to 40 nm or more, damage to the porous body 10 can be suppressed even when the analytical carrier 1 is bent. This makes it easy to prevent the outer shell 14 from breaking and leaving wrinkles when the analytical carrier 1 undergoes bending deformation. Further, by setting the thickness of the outer shell 14 in such a range, the analytical carrier 1 with sufficiently high corrosion resistance can be provided. The thickness of the outer shell 14 may be 100 nm or more, 200 nm or more, or 400 nm or more. In addition, the thickness of the outer shell 14 may be 900 nm or less, 700 nm or less, or 500 nm or less. When the thickness of the outer shell 14 is equal to or less than the above upper limit value, when the outer shell is formed by performing the anodizing step and the dissolving step once each or alternately and repeatedly, the anodized film is not formed to be excessively thick, the aluminum portion of the metal can be dissolved to form the outer shell with a desired thickness, and the production efficiency can be easily improved. The thickness of the outer shell 14 can be measured, for example, by observing a cross section of the outer shell 14 with a scanning electron microscope or the like.
[0025] The cumulative pore surface area of pores having a pore diameter of 0.1 μm or more and 100 μm or less in the porous body 10 may be 0.1 m 2 / cm 3 or more and 20 m 2 / cm 3 or less. When the cumulative pore surface area of the porous body 10 is 0.1 m 2 / cm 3 or more, the amount of antibody adsorbed to the porous body 10 increases. Thereby, the absorbance of the analytical carrier 1 can be improved. When the cumulative pore surface area of the porous body 10 is 20 m 2 / cm 3 or less, the water absorbency of the porous body 10 can be improved. The cumulative pore surface area may be 0.5 m 2 / cm 3 or more, or 1 m 2 / cm 3 or more. In addition, the cumulative pore surface area may be 10 m 2 / cm 3 or less, or 6 m 2 / cm3 The following is also possible: The cumulative pore surface area of the porous body 10 can be obtained by converting the pore volume of pores having a pore diameter of 0.1 μm or more and 100 μm or less, obtained by the mercury intrusion method, into a surface area for each pore diameter and accumulating them.
[0026] The porosity of the porous body 10 is 50% by volume or more and less than 100% by volume. By setting the porosity of the porous body 10 to 50% by volume or more, the water absorption performance can be improved. By setting the porosity to less than 100% by volume, the peeling of hollow particles 13 from the porous body 10 can be suppressed and the strength of the porous body 10 can be improved. The porosity may be 60% by volume or more, 70% by volume or more, 80% by volume or more, 90% by volume or more, or 95% by volume or more. Alternatively, the porosity may be 95% by volume or less, 90% by volume or less, or 80% by volume or less. The porosity of the porous body 10 can be obtained by dividing the cumulative pore volume of the porous body 10 by the volume of the porous body 10. The cumulative pore volume of the porous body 10 can be obtained by integrating the pore volumes of pores having a pore diameter of 0.1 μm or more and 100 μm or less, which are obtained by measurement using the mercury intrusion method.
[0027] The average pore size of the porous body 10 is between 0.1 μm and 20 μm. By setting the average pore size to 0.1 μm or more, the water absorption performance of the analytical carrier 1 can be improved. Here, the particle size of labels such as colored particles, gold colloid particles, or fluorescent beads commonly used in immunochromatography is about 10 nm to 50 nm, and there are also labels with larger particle sizes. When the analytical carrier 1 is used, for example, as a test strip for immunochromatography, setting the average pore size to 0.1 μm or more suppresses the trapping of such labels in the voids 12, allowing the labels to flow smoothly through the porous body 10. Furthermore, by setting the average pore size to 20 μm or less, the water absorption performance of the analytical carrier 1 can be improved. The average pore size may be 0.5 μm or more, 1 μm or more, 3 μm or more, or 5 μm or more. Furthermore, the average pore diameter may be 15 μm or less, 12 μm or less, 10 μm or less, or 9 μm or less. The average pore diameter of the porous body 10 can be calculated by the following formula. Average pore diameter of porous material 10 = 4 × (cumulative pore volume of porous material 10) / (cumulative pore surface area of porous material 10) The cumulative pore volume and cumulative pore surface area of the porous body 10 can be obtained as described above.
[0028] The ratio of the cumulative surface area of pores having a diameter of 0.1 μm or more but less than 1 μm to the cumulative surface area of pores having a diameter of 1 μm or more but less than 1 μm may be between 0.1 and 10. The ratio of cumulative surface areas may be between 0.2 or more, 0.5 or more, or 1 or more. The ratio of cumulative surface areas may be between 8 or less, 6 or less, or 5 or less. The cumulative surface area of pores having a diameter of 1 μm or more but less than 10 μm can be obtained by integrating the surface areas of pores having a diameter of 1 μm or more but less than 10 μm. Similarly, the cumulative surface area of pores having a diameter of 0.1 μm or more but less than 1 μm can be obtained by integrating the surface areas of pores having a diameter of 0.1 μm or more but less than 1 μm. The cumulative surface area of the porous body 10 can be determined by the mercury intrusion method as described above. The absorbance and other signals from the analytical carrier 1 tend to be proportional to the flow rate. Furthermore, in order to lower the flow rate, in other words, to increase the rate at which water is drawn up, it is necessary to increase the porosity. That is, there is a trade-off relationship where analytical carrier 1, which has high porosity and a fast rate of water drawn up, will have a lower signal. When the ratio of cumulative pore surface area is above the lower limit, the surface area of the porous body 10 increases, the amount of antibody bound to the porous body 10 increases, and the signal from the analytical carrier 1 becomes stronger. In addition, even if the analytical carrier 1 has a flow rate similar to that of a nitrocellulose membrane, a higher absorbance than that of a nitrocellulose membrane can be obtained if the ratio of cumulative pore surface area is above the lower limit. By keeping the ratio of cumulative pore surface area below the upper limit, clogging of labeled particles can be prevented.
[0029] The thickness of the porous body 10 is preferably 20 μm or more and 190 μm or less. By making the thickness of the porous body 10 20 μm or more, it is easier to ensure sufficient thickness for water to be drawn up by capillary action. By making the thickness of the porous body 10 190 μm or less, it is possible to suppress the analytical carrier 1 appearing gray when the porous body 10 absorbs water. In addition, by making the thickness of the porous body 10 190 μm or less, it is possible to suppress the porous body 10 from cracking and forming fissures when the analytical carrier 1 is bent, which would leave wrinkles. The thickness of the porous body 10 may be 30 μm or more, 40 μm or more, or 50 μm or more. The thickness of the porous body 10 may be 150 μm or less, or 100 μm or less.
[0030] The porous body 10 may consist of a single porous layer, or it may contain multiple porous layers. The porous body 10 may, for example, comprise a first porous layer and a second porous layer disposed on the surface of the first porous layer. The first porous layer and the second porous layer may differ in any of the following: the average particle diameter, aspect ratio, or constituent material of the multiple hollow particles 13, the porosity of the porous body 10, or the average pore diameter. For example, the average particle diameter of the hollow particles 13 contained in the first porous layer may be greater than the average particle diameter of the hollow particles 13 contained in the second porous layer. Furthermore, the thicknesses of the first porous layer and the second porous layer may be the same or different.
[0031] The porous body 10 is provided on the surface opposite to the support 20 and may include a coating layer 17 containing an anodic oxide film containing aluminum oxide, separating the inside of the porous body 10, where the skeleton 11 and voids 12 exist, from the outside of the porous body 10. The coating layer 17 may have communication holes 18 that connect the inside and outside of the porous body 10. The coating layer 17 may be formed continuously with the outer shell 14 of the hollow particles 13. The cavities 15 of the hollow particles 13 may communicate with the outside of the porous body 10 through the communication holes 18. Because the porous body 10 includes a coating layer 17, the hollow particles 13 are not exposed to the outside, and direct contact of fingers or other objects with the porous body 10 can be suppressed. This can suppress the peeling of the hollow particles 13. Therefore, the handling of the analytical carrier 1 can be improved.
[0032] The surface roughness Sa of the porous body 10 may be 0.01 μm or more and less than 1.8 μm. When the surface roughness Sa of the porous body 10 is less than 1.8 μm, the hollow particles 13 are not exposed on the surface of the porous body 10, and the surface of the porous body 10 tends to be covered by the coating layer 17. This makes it difficult for the hollow particles 13 of the porous body 10 to peel off from the porous body 10, the support 20, or the analytical carrier 1. The surface roughness Sa of the porous body 10 may be 0.1 μm or more, 0.2 μm or more, 0.4 μm or more, 0.6 μm or more, or 0.8 μm or more. In addition, the surface roughness Sa of the porous body 10 may be 1.5 μm or less, 1.2 μm or less, or 1 μm or less. The arithmetic mean roughness Sa can be obtained by measuring the surface of the porous body 10 opposite to the support 20 in accordance with ISO 25178.
[0033] <Support> The support 20 supports the porous body 10 on one side. By supporting the porous body 10 with the support 20, damage to the porous body 10 due to deformation or other factors can be suppressed. The support 20 includes an adhesive layer 22 that adheres to the porous body 10. The adhesive layer 22 adheres to the outer shell 14 of the porous body 10.
[0034] The support 20 may include an adhesive layer 22 that adheres to the porous body 10 and a support layer 21 that supports the adhesive layer 22. In this case, the adhesive layer 22 is interposed between the porous body 10 and the support layer 21. The porous body 10 and the support layer 21 are firmly bonded together by the adhesive layer 22. Alternatively, the support 20 may consist only of the adhesive layer 22 without including the support layer 21.
[0035] The adhesive layer 22 has adhesive portions 23 in which the material constituting the adhesive layer 22 penetrates the voids 12 and cavities 15 of the porous body 10, comes into contact with the hollow particles 13 and outer shells 14, and adheres to the hollow particles 13 and outer shells 14. The adhesive portions 23 are portions in which the material constituting the adhesive layer 22 and the hollow particles 13 and outer shells 14 are mixed together along the direction of the adhesive interface between the porous body 10 and the adhesive layer 22.
[0036] The adhesive layer 22 may have an adhesive portion 23 and an auxiliary portion 24. The auxiliary portion 24 is made of the material constituting the adhesive layer 22 and is continuous with the adhesive portion 23, assisting adhesion by backing the adhesive portion 23 from the side opposite to the porous body 10. The auxiliary portion 24 is a portion made of the material constituting the adhesive layer 22 that exists along the direction of the adhesive interface between the porous body 10 and the adhesive layer 22. The auxiliary portion 24 is provided in the adhesive layer 22 on the side opposite to the adhesive portion 23 that is in contact with the porous body 10. The auxiliary portion 24 is positioned between the adhesive portion 23 and the support layer 21, and by the adhesion between the auxiliary portion 24 and the support layer 21, it also functions as a layer that adheres the adhesive portion 23 and the support layer 21. The auxiliary portion 24 also functions as a layer that adheres the adhesive layer 22 and the support layer 21.
[0037] For example, when a thermoplastic resin is used as the adhesive layer 22 to bond the adhesive layer 22 to the porous body 10, when the heated adhesive layer 22 comes into contact with the porous body 10, the portion of the softened thermoplastic resin that comes into contact with the porous body 10 deforms and enters the voids 12 and cavities 15 of the porous body 10, and hardens as the temperature decreases. At this time, as the thermoplastic resin enters the voids 12 and cavities 15 of the porous body 10, the portion of the layer in which the thermoplastic resin, hollow particles 13 and outer shell 14 are in contact while mixed together becomes the adhesive portion 23. On the other hand, when bonding the adhesive layer 22 to the porous body 10, the portion of the thermoplastic resin that does not come into contact with the porous body 10 and maintains its thermoplastic resin layer, and which is continuous with the adhesive portion 23, becomes the auxiliary portion 24.
[0038] For example, when using an adhesive (tack) as the adhesive layer 22 to bond the adhesive layer 22 to the porous body 10, when the adhesive layer 22 comes into contact with the porous body 10, the portion of the adhesive that comes into contact with the porous body 10 deforms and enters the voids 12 and cavities 15 of the porous body 10. At this time, as the adhesive enters the voids 12 and cavities 15 of the porous body 10, the portion of the layer in which the adhesive, hollow particles 13, and outer shell 14 are in contact while mixed together is designated as the adhesive portion 23. On the other hand, when bonding the adhesive layer 22 to the porous body 10, the portion of the adhesive that does not come into contact with the porous body 10, maintains its adhesive layer, and is continuous with the adhesive portion 23 is designated as the auxiliary portion 24.
[0039] The thickness of the adhesive layer 22 may be 1 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, or 30 μm or more. Alternatively, the thickness of the adhesive layer 22 may be 1000 μm or less, 500 μm or less, 300 μm or less, 200 μm or less, 100 μm or less, 50 μm or less, or 40 μm or less. The thickness of the adhesive layer 22 is usually greater than the thickness of the adhesive portion 23. When the thickness of the adhesive layer 22 is greater than or equal to the above lower limit, the adhesive layer 22 adheres to the porous body 10, and when the support 20 is deformed, the adhesive layer 22 mitigates the deformation, suppressing the strain generated between the support 20 and the porous body 10, thereby making it easier to maintain adhesion between the support 20 and the porous body 10. This makes it easier to suppress the porous body 10 from peeling off the support 20 when the support 20 is deformed. It also makes it easier to suppress the occurrence of wrinkles in the porous body 10 when the support 20 is deformed. The thickness of the adhesive layer is below the above upper limit, allowing it to bend appropriately during roll-to-roll production, making it easy to transport. The thickness of the adhesive layer 22 refers to the total thickness in the thickness direction of the material constituting the adhesive layer 22 when observed in cross-section in a plane perpendicular to the direction of the adhesive interface between the porous body 10 and the adhesive layer 22.
[0040] The thickness of the adhesive portion 23 may be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, or 10 μm or more. Alternatively, the thickness of the adhesive portion 23 may be 100 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less. When the thickness of the adhesive portion 23 is equal to or greater than the above lower limit, it will make contact with the outer shell 14 with a sufficient thickness so that the adhesive portion 23 is equal to or greater than the thickness of the outer shell 14. At this time, as the adhesive portion 23 penetrates to a deep position in the outer shell 14, the anchoring effect of the adhesive portion 23 is exerted, making it easier for the porous body 10 and the support 20 to be firmly bonded. In addition, as the contact area between the outer shell 14 and the adhesive portion 23 increases, the action of the adhesive portion 23 by hydrogen bonds, van der Waals forces, ionic bonds, or covalent bonds is strengthened, making it easier for the porous body 10 and the support 20 to be firmly bonded. This makes it easier to prevent the porous body 10 from peeling off the support 20 when the support 20 is deformed. It also makes it easier to prevent wrinkles from forming in the porous body 10 when the support 20 is deformed. By keeping the thickness of the adhesive portion 23 below the above upper limit, it is possible to prevent the porous body 10 from being completely filled with resin. The thickness of the adhesive portion 23 refers to the distance between a line that passes through the part of the porous body 10 closest to the adhesive layer 22 (the bottom) and is parallel to the direction of the adhesive interface between the porous body 10 and the adhesive layer 22, and a line that passes through the part of the adhesive layer 22 closest to the porous body 10 (the top) and is parallel to the direction of the adhesive interface between the porous body 10 and the adhesive layer 22, when a cross-sectional observation is made in a plane perpendicular to the direction of the adhesive interface between the porous body 10 and the adhesive layer 22, in the area where the material constituting the adhesive layer 22 is in contact with the porous body 10.
[0041] The thickness of the support layer 21 may be 10 μm or more, 50 μm or more, 70 μm or more, 90 μm or more, or 100 μm or more. Alternatively, the thickness of the support layer 21 may be 1000 μm or less, 500 μm or less, 300 μm or less, 200 μm or less, 150 μm or less, or 100 μm or less.
[0042] The support 20 may be flexible. When a porous body is arranged on the surface of an aluminum substrate, such as in the aluminum member described in International Publication No. 2021 / 079813, bending the analytical carrier 1 may cause the aluminum substrate to plastically deform and not return to its original shape. In this case, the porous body arranged on the surface of the aluminum substrate will also wrinkle as it follows the aluminum substrate. On the other hand, if the analytical carrier 1 is flexible, it is easier for the analytical carrier 1 to return to its original shape even after bending deformation, thus preventing wrinkles from forming on the support 20. The support 20 supports the porous body 10, and since the support 20 is less prone to wrinkles, it is possible to suppress the formation of wrinkles on the porous body 10 of the analytical carrier 1.
[0043] The support 20 contains a resin or elastomer that is resistant to organic solvents. With this configuration, even when an organic solvent is used as the developing solvent, analysis can be performed while avoiding the influence of the organic solvent absorption performance on both the porous body 10 and the support 20. The support layer 21 contained in the support 20 may contain a resin or elastomer that is resistant to organic solvents. The adhesive layer 22 contained in the support 20 may contain a resin or elastomer that is resistant to organic solvents.
[0044] At least one of the support layer 21 and the adhesive layer 22 may not substantially contain a resin or elastomer that is not resistant to organic solvents. "At least one of the support layer 21 and the adhesive layer 22 may not substantially contain a resin or elastomer that is not resistant to organic solvents" means that the amount of "a resin or elastomer that is not resistant to organic solvents contained in at least one of the support layer 21 and the adhesive layer 22" is 5% by mass or less. The amount of "a resin or elastomer that is not resistant to organic solvents contained in at least one of the support layer 21 and the adhesive layer 22" may be 0% by mass or more and 3% by mass or less, 0% by mass or more and 1% by mass or less, or 0% by mass.
[0045] The support 20 may not substantially contain any resin or elastomer that is not resistant to organic solvents. "The support 20 may not substantially contain any resin or elastomer that is not resistant to organic solvents" means that the amount of "resin or elastomer that is not resistant to organic solvents contained in the support 20" is 5% by mass or less. The amount of "resin or elastomer that is not resistant to organic solvents contained in the support 20" may be 0% by mass or more and 3% by mass or less, 0% by mass or more and 1% by mass or less, or 0% by mass.
[0046] Resins or elastomers with organic solvent resistance may exhibit a weight loss of less than 10% in each of the following immersion tests: immersion in methanol, ethanol, and acetone, standing at room temperature for 5 minutes, and then drying at 50°C for 10 minutes. Such resins or elastomers have high resistance to the above organic solvents. Therefore, even when an organic solvent is used as the developing solvent, analysis can be performed while avoiding the influence of the organic solvent's absorption performance on both the porous body 10 and the support 20. The weight loss in the immersion test may be less than 5% or even less than 0.5% for each solvent. The smaller the weight loss, the higher the organic solvent resistance, and thus the greater the influence of the organic solvent's absorption performance.
[0047] The support 20 is made of polyethylene (HDPE, MDPE, LDPE), polypropylene, modified polyolefin resins (modified polypropylene, modified polyethylene, etc.), ethylene vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyamide, polyester (PET), (meth)acrylic resin, epoxy resin, urethane resin, fluororesin, styrene resin, ABS resin, silicone resin, phenolic resin, melamine resin, polyvinyl alcohol, polycyanoacrylate, isocyanate adhesive, urethane resin adhesive, urethane resin solvent adhesive, urethane resin emulsion adhesive, acrylic resin adhesive, acrylic resin anaerobic adhesive, olefin adhesive, silicone The material may contain at least one selected from the group consisting of polystyrene-based adhesives, rubber-based adhesives, ethylene vinyl acetate resin emulsion adhesives, epoxy resin-based adhesives, epoxy resin emulsion adhesives, vinyl chloride resin solvent-based adhesives, chloroprene rubber-based adhesives, cyanoacrylate-based adhesives, aqueous polymer-isocyanate-based adhesives, styrene-butadiene rubber solution-based adhesives, styrene-butadiene rubber latex adhesives, nitrile rubber-based adhesives, nitrocellulose adhesives, phenol resin-based adhesives, modified silicone-based adhesives, polyimide-based adhesives, polystyrene resin solvent-based adhesives, polybenzimidazole adhesives, polymethacrylate resin solution-based adhesives, and light- and ultraviolet-curing resin-based adhesives. These materials have high resistance to organic solvents. Therefore, even when an organic solvent is used as the developing solvent, analysis can be performed while avoiding the influence of the organic solvent on the absorption performance of both the porous body 10 and the support 20.The support 20 is made of polyethylene (HDPE, MDPE, LDPE), polypropylene, polyvinyl chloride, polyamide, polyester (PET), (meth)acrylic resin, epoxy resin, urethane resin, fluororesin, styrene resin, ABS resin, silicone resin, phenolic resin, melamine resin, polyvinyl alcohol, polycyanoacrylate, isocyanate adhesive, urethane resin adhesive, urethane resin solvent adhesive, urethane resin emulsion adhesive, olefin adhesive, silicone adhesive, rubber adhesive, epoxy resin adhesive, epoxy resin emulsion It is preferable to include at least one selected from the group consisting of John adhesives, vinyl chloride resin solvent-based adhesives, chloroprene rubber-based adhesives, cyanoacrylate-based adhesives, aqueous polymer-isocyanate-based adhesives, styrene-butadiene rubber solution-based adhesives, styrene-butadiene rubber-based latex adhesives, nitrile rubber-based adhesives, nitrocellulose adhesives, phenol resin-based adhesives, modified silicone-based adhesives, polyimide-based adhesives, polystyrene resin solvent-based adhesives, polybenzimidazole adhesives, polymethacrylate resin solution-based adhesives, and light- and ultraviolet-curing resin-based adhesives.
[0048] The adhesive layer 22 may contain at least one selected from the group consisting of resins, elastomers, starch, and proteins. That is, the adhesive layer 22 may be a resin adhesive layer or an elastomer adhesive layer. The resin may contain at least one selected from the group consisting of thermoplastic resins, thermosetting resins, and UV-curing resins. The UV-curing resin may contain at least one of radical-curing resins and cationic-curing resins. The resin may contain at least one selected from the group consisting of polyethylene (HDPE, MDPE, LDPE), polyolefins such as polypropylene and modified polyolefin resins (modified polypropylene, modified polyethylene, etc.), ethylene vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyamide, polyester, (meth)acrylic resin, epoxy resin, urethane resin, fluororesin, styrene resin, ABS resin, silicone resin, phenolic resin, melamine resin, polyvinyl alcohol, and polycyanoacrylate. Furthermore, the resin may include adhesives such as isocyanate adhesives, urethane resin adhesives, urethane resin solvent adhesives, urethane resin emulsion adhesives, acrylic resin adhesives, anaerobic acrylic resin adhesives, olefin adhesives, silicone adhesives, rubber adhesives, ethylene vinyl acetate resin emulsion adhesives, epoxy resin adhesives, epoxy resin emulsion adhesives, vinyl chloride resin solvent adhesives, chloroprene rubber adhesives, cyanoacrylate adhesives, aqueous polymer-isocyanate adhesives, styrene-butadiene rubber solution adhesives, styrene-butadiene rubber latex adhesives, nitrile rubber adhesives, nitrocellulose adhesives, phenol resin adhesives, modified silicone adhesives, polyimide adhesives, polystyrene resin solvent adhesives, polybenzimidazole adhesives, polymethacrylate resin solution adhesives, and light- and ultraviolet curing resin adhesives. The elastomer may include at least one selected from the group consisting of thermoplastic elastomers and rubber. The adhesive layer 22 may contain ethylene vinyl acetate copolymer. Since the ethylene vinyl acetate copolymer melts at a relatively low temperature, the porous body 10 and the support layer 21 can be easily bonded together.If the adhesive layer 22 contains a thermoplastic resin, it is preferable that the melting point of the adhesive layer 22 is lower than the melting point of the support 20. From the viewpoint of suppressing deformation of the support 20 when the analytical carrier 1 is subjected to bending deformation, it is preferable that the adhesive layer 22 contains a highly flexible material.
[0049] The support layer 21 may contain at least one material selected from the group consisting of resin, elastomer, metal, and paper. These materials can effectively support the porous body 10. From the viewpoint of suppressing deformation of the support 20 when the analytical carrier 1 is subjected to bending deformation, it is preferable that the support layer 21 contains a material that does not easily undergo plastic deformation when a certain strain is applied. Furthermore, when the analytical carrier 1, in which the porous body 10 has absorbed water, is placed on a white reflectance standard, the L value measured is... * From the viewpoint of improving the value, the support layer 21 preferably contains a material with high light transmittance or a material with high whiteness. The resin or elastomer preferably has resistance to organic solvents. The resin may contain at least one selected from the group consisting of thermoplastic resins, thermosetting resins and UV-curable resins. The resin may contain at least one selected from the group consisting of polyester (PET), acrylic resin, urethane resin, silicone resin, epoxy resin, polyolefin, cellulose resin, styrene resin, polyimide, and polycarbonate. The elastomer may contain at least one selected from the group consisting of thermoplastic elastomers and rubber. The metal may contain, for example, at least one selected from the group consisting of aluminum, iron, copper, gold, silver, and zinc.
[0050] The support layer 21 may be a single layer or a multilayer layer. If the support layer 21 is a multilayer layer, the materials of each layer may be the same or different. If the support layer 21 is a multilayer layer, it is preferable that the melting point of the material located closest to the adhesive layer 22 is lower than that of the material located furthest away from the adhesive layer 22. The support layer 21 may be, for example, a two-layer layer of LDPE (low-density polyethylene) and PET (polyethylene terephthalate). This arrangement can suppress the adhesive layer 22 from overflowing during lamination.
[0051] The resin contained in the support layer 21 may contain fillers. The fillers may contain at least one of organic fillers and inorganic fillers. The organic fillers may contain at least one selected from the group consisting of resin fillers, cellulose nanofibers, and dyes. The inorganic fillers may contain at least one selected from the group consisting of oxides, hydroxides, carbides, nitrides, borides, silicides, and fluorides. The fillers may be spherical, polygonal, irregular in shape, flaky, needle-like, or fibrous. The support layer 21 may be plate-like, sheet-like, woven, or nonwoven.
[0052] <Analytical Carrier> The analytical carrier 1 comprises a porous body 10 and a support 20. The support 20 includes an adhesive layer 22. The support 20 may also include an adhesive layer 22 and a support layer 21. The adhesive layer 22 of the support 20 is bonded to the outer shell 14 of the porous body 10. The porous body 10 and the support 20 may be laminated by bonding with the adhesive layer 22 bonded to the outer shell 14 and the adhesive layer 22 interposed between the porous body 10 and the support layer 21. The adhesive layer 22 may include an adhesive portion 23 and an auxiliary portion 24. The support 20 includes an adhesive layer 22 including the adhesive portion 23 and the auxiliary portion 24, and a support layer 21, and the adhesive portion 23, the auxiliary portion 24, and the support layer 21 may be laminated in this order. The adhesive portion 23 and the outer shell 14 are bonded together, and the auxiliary portion 24 and the support layer 21 are bonded together, so the porous body 10, adhesive portion 23, auxiliary portion 24, and support layer 21 may be laminated in this order.
[0053] The adhesive layer 22 may be bonded to the outer shell 14 located on the side of the porous body 10 opposite to the coating layer 17. The porous body 10 may have its outer shell 14 bonded to the adhesive layer 22, and the coating layer 17 located on the side opposite to the outer shell 14 bonded to the adhesive layer 22 may be exposed. In the analytical carrier 1, with the porous body 10 and the support 20 bonded together, the coating layer 17 may be located on the side opposite to the support 20 and on the outside of the porous body 10, while the hollow particles 13 and outer shell 14 may be located on the inside of the porous body 10 sandwiched between the coating layer 17 and the support 20. Thus, in the analytical carrier 1, the coating layer 17 is located on the outside of the porous body 10, the hollow particles 13 and outer shell 14 are located on the inside of the porous body 10, and the hollow particles 13 and outer shell 14 are covered by the coating layer 17 provided on the surface of the analytical carrier 1. This suppresses the detachment of the hollow particles 13 from the porous body 10, support 20, or analytical carrier 1, thereby improving handling.
[0054] The thickness of the analytical support 1 may vary depending on the application, but for example, it may be between 20 μm and 10 cm. By setting the thickness of the analytical support 1 within this range, an analytical support 1 with good bending strength can be provided. The thickness of the analytical support 1 may be 30 μm or more, 50 μm or more, 100 μm or more, or 150 μm or more. The thickness of the analytical support 1 may be 1000 μm or less, 300 μm or less, or 200 μm or less.
[0055] A porous body 10 is provided on one side of the support 20, which is the first surface, and the second surface, which is the opposite side of the first surface, may be exposed. With this configuration, the analytical support 1 can improve problems caused by reattaching the porous body 10. Specifically, when preparing an immunochromatography test strip or test kit, the adhesive members that make up the immunochromatography test strip or test kit are attached to the support 20. However, when trying to peel off the adhesive members attached to the support 20 and reattach them for position adjustment or other reasons, it can be difficult to reattach them.
[0056] For example, if the porous body 10 is provided on both sides of the aluminum substrate described later, and the adhesive member is attached to the porous body 10 on one side of the aluminum substrate and then peeled off, the porous body 10 may peel off from the aluminum substrate. In such cases, the porous body 10 remains on the adhesive member, which may weaken the adhesive strength of the adhesive member. Also, if the porous body 10 is provided on one side of the aluminum substrate, and the adhesive member is attached to the side of the aluminum substrate where the porous body 10 is not provided and then peeled off, the aluminum substrate may undergo plastic deformation. In such cases, wrinkles may form on the porous body 10.
[0057] On the other hand, if the porous body 10 is provided on the first surface of the support 20 and the second surface of the support 20 is exposed, the problems caused by re-attaching as described above can be suppressed by attaching the adhesive member to the support 20. Note that the first and second surfaces may be main surfaces. Here, the main surfaces are the surfaces perpendicular to the thickness direction of the support 20, and are the two surfaces with the first and second largest areas among the six surfaces forming the support 20.
[0058] When the analytical carrier 1, which has absorbed water from the porous body 10, is placed on a white reflective standard for which the measuring instrument has been calibrated, the surface of the porous body 10 on the analytical carrier 1 is measured with the measuring instrument, and L is measured. * a * b * L in color systems* The value may be 75 or higher. * By setting the value to 75 or higher, the discriminability during water absorption can be improved. * The value may be 80 or greater, 85 or greater, 90 or greater, or 95 or greater. In this specification, L * a * b * L in color systems * The value can be measured using a colorimeter with a 45° circular illumination and vertical light reception method compliant with JIS Z8722. Furthermore, the analytical carrier 1, in which the porous body 10 has absorbed water, can be obtained by allowing the porous body 10 to absorb pure water. Note that when a calibrated white reflectance standard is measured with the measuring instrument, the L value is... * a * b * L in color systems * The value is 97.1.
[0059] When the porous material 10 is dried and placed on a white reflective standard with a calibrated measuring instrument, the surface of the porous material 10 on the analytical instrument is measured with the measuring instrument, and L * a * b * L in color systems * The value may be 75 or higher. * By setting the value to 75 or higher, the discriminability during water absorption can also be improved. * The value may be 80 or higher, 85 or higher, 90 or higher, or 95 or higher. Note that "dry" means that the porous body 10 has not absorbed any water.
[0060] When the analytical carrier 1, which has absorbed water from the porous body 10, is placed on a white reflective standard for which the measuring instrument has been calibrated, the surface of the porous body 10 on the analytical carrier 1 is measured with the measuring instrument, and L is measured. * a * b * L in color systems *The value may be less than 75. Also, when the porous material 10 is placed on a white reflective standard with a calibrated measuring instrument, the surface of the porous material 10 on the analytical carrier 1 is measured with the measuring instrument. * a * b * L in color systems * The value may be less than 75. With this configuration, even if fluorescence is emitted from the backing sheet to which the analytical carrier 1 is attached, L * Because the value is less than 75, fluorescence is less likely to pass through. Therefore, it is possible to suppress the increase in background and decrease in the signal-to-noise ratio when performing fluorescence measurements. At least one of these L * The value may be 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, or 10 or less.
[0061] In the analytical carrier 1, it is preferable that the time required to draw up water to a height of 4 cm by capillary action is 400 seconds or less. By doing so, an analytical carrier 1 suitable for chromatography, for example, can be provided. This time may be 20 seconds or more, 40 seconds or more, or 50 seconds or more. Alternatively, this time may be 360 seconds or less, 200 seconds or less, or 100 seconds or less. This time can be obtained, for example, by immersing the analytical carrier 1 in pure water at room temperature (30°C) such that the planar direction of the analytical carrier 1 is perpendicular to the liquid surface, and measuring the time required to draw up water to a height of 4 cm by capillary action. The pure water is pure water with a resistivity of 10 kΩm measured at 30°C.
[0062] As shown in Figures 13 and 14, it is preferable that the porous body 10 of the analytical carrier 1 does not peel off during the bending test. It is also preferable that no wrinkles remain on the surface of the porous body 10 of the analytical carrier 1 during the bending test. Specifically, in the bending test, 10g weights 230 are attached to both ends of the analytical carrier 1, which has been cut to 10mm x 100mm. The analytical carrier 1 is then placed on the stainless steel rod 240 so that the porous body 10 is in contact with the stainless steel rod 240 at the longitudinal center of the analytical carrier 1, and the carrier 1 is lifted until the weights 230 at both ends are lifted off the ground and held for 10 seconds. After holding for 10 seconds, the stainless steel rod 240 is returned to its original position, and the surface of the porous body 10 is visually observed and evaluated. An analytical carrier 1 in which the porous body 10 does not peel off during the bending test is easier to handle because the porous body 10 is less likely to peel off when bending or reattaching. Furthermore, an analytical carrier 1 that does not retain wrinkles on the surface of the porous body 10 during a bending test is less prone to wrinkles when bent or reattached, thus facilitating the handling of the analytical carrier 1. Note that delamination of the porous body 10 refers to the separation of the adhesive layer 22 from the porous body 10, specifically when the minimum width of the separated portion within the plane of the analytical carrier 1 is 2 mm or more and the maximum length is 5 mm or more. Wrinkles on the porous body 10 refer to wrinkles of a millimeter order size that are visible to the naked eye.
[0063] The porous body 10 can be used to flow a developing solution containing an organic solvent. The organic solvent may contain at least one of ethanol and ketones. The ethanol may contain at least one selected from the group consisting of methanol and ethanol, for example. The ketone may contain acetone, for example. The porous body 10 can also be used to flow a developing solution containing water. Therefore, the developing solution may contain at least one of an organic solvent and water.
[0064] <Effects and Effects> As described above, the analytical carrier 1 according to this embodiment comprises a porous body 10 and a support 20 that supports the porous body 10 on one side. The porous body 10 includes a skeleton 11 formed by the aggregation of a plurality of hollow particles 13, and a plurality of voids 12 surrounded by the skeleton 11. The hollow particles 13 have an outer shell 14 including an anodic oxide film containing aluminum oxide, and a cavity 15 surrounded by the outer shell 14. The skeleton 11 is formed by the continuous arrangement of outer shells 14 made up of a plurality of hollow particles 13. The porosity of the porous body 10 is 50% by volume or more and less than 100% by volume. The average pore diameter of the porous body 10 is 0.1 μm or more and 20 μm or less. The support 20 includes an adhesive layer 22 that adheres to the porous body 10, and the adhesive layer 22 adheres to the outer shell 14. The support 20 includes a resin or elastomer that is resistant to organic solvents.
[0065] As described in International Publication No. 2021 / 079813, in an aluminum member in which a porous body is supported by an aluminum substrate, and the aluminum oxide of the porous body and the aluminum oxide of the aluminum substrate are integrated, when the aluminum member is subjected to bending deformation, the portion of aluminum oxide connecting the porous body and the aluminum substrate may break, causing the porous body to peel off from the aluminum substrate.
[0066] In this embodiment, the analytical carrier 1 includes a support 20 that supports the porous body 10. The support 20 includes an adhesive layer 22 that adheres to the porous body 10, and the adhesive layer 22 is adhered to the outer shell 14. In this way, since the porous body 10 is supported by the support 20 while being adhered by the adhesive layer 22, when the analytical carrier 1 is subjected to bending deformation, the deformation (strain) that occurs between the porous body 10 and the support 20 is mitigated by the adhesive layer 22, making it easier to avoid fracture between the porous body 10 and the support 20. Therefore, in this embodiment, the analytical carrier 1 can suppress the peeling of the porous body 10 from the support 20 even when subjected to bending deformation.
[0067] Furthermore, the analytical carrier 1 according to this embodiment includes hollow particles 13 having an outer shell 14 containing an anodic oxide film containing aluminum oxide in the porous body 10. Aluminum oxide has high resistance to organic solvents. In addition, the analytical carrier 1 according to this embodiment includes a support 20 containing a resin or elastomer that is resistant to organic solvents. As a result, even when an organic solvent is used as the developing solvent, analysis can be performed while avoiding the influence of the organic solvent absorption performance on both the porous body 10 and the support 20.
[0068] Antigens that are highly lipophilic (soluble in organic solvents) and have low water solubility were difficult to analyze when using conventional nitrocellulose membrane filter testing kits to develop an aqueous solution, because the antigen did not dissolve easily in the aqueous solution. Furthermore, when attempting to analyze such antigens using conventional nitrocellulose membrane filter testing kits by developing an organic solvent, the nitrocellulose membrane itself dissolved in the organic solvent, making analysis difficult. According to the analytical carrier 1 of this embodiment, it becomes possible to dissolve such antigens in an organic solvent and perform analysis.
[0069] Furthermore, when analyzing antigens that are highly lipophilic (soluble in organic solvents) and low water-soluble using conventional nitrocellulose membrane filters, the antigen extracted with an organic solvent was diluted with an aqueous solution before development. However, this dilution made it difficult to achieve high sensitivity. With the analytical carrier 1 according to this embodiment, it is possible to flow it at high concentrations using an organic solvent, thus enabling analysis with high sensitivity.
[0070] [2. Test strips for immunochromatography] The immunochromatography test strip is equipped with an analytical carrier 1. The analytical carrier 1 allows for the analysis of the analyte while it is supported. The analytical carrier 1 can suppress the peeling of the porous body 10 from the support 20 even when subjected to bending deformation, making it suitable for use as an immunochromatography test strip. The immunochromatography test strip is also called an immunochromatography developing member, a lateral flow assay test strip, or a lateral flow assay developing member. Furthermore, the analytical carrier 1 is preferably used in in vitro diagnostic pharmaceuticals such as test kits that utilize immunochromatography.
[0071] [3. Test kit] Next, an example of a test kit 50 using the analytical carrier 1 will be described. The test kit 50 is sometimes also called a diagnostic kit. As shown in Figure 2, the test kit 50 includes a test strip 60 having the analytical carrier 1. Specifically, the test strip 60 includes the analytical carrier 1, a sample supply section 62, and an absorption section 64. The analytical carrier 1 is provided with a determination section 66. The test kit 50 may further include a case (not shown) for housing the test strip 60.
[0072] The sample supply unit 62 may contain, for example, a labeled antibody that specifically binds to the antigen, which is the analyte. A sample collected from a living organism or the like is supplied to the sample supply unit 62, mixed with the labeled antibody, and becomes a mixed solution. The mixed solution is spread to the detection unit 66 by the capillary action of the analytical carrier 1, and any excess sample is absorbed into the absorption unit 64.
[0073] The detection unit 66 has, for example, a test line and a control line. The test line has, for example, a capture antibody that specifically binds to the analyte immobilized on it. If the sample contains the analyte, the labeled antibody is immobilized on the capture antibody on the test line via the analyte. The control line has, for example, an antibody that specifically binds to the labeled antibody immobilized on it. When the mixture containing the sample and the labeled antibody is spread to the control line, the labeled antibody binds to the antibody immobilized on the control line.
[0074] A labeled antibody contains a label, such as a colored particle, a gold colloid particle, or a fluorescent bead, and an antibody that binds to this label to form a complex and also specifically binds to the analyte. Therefore, if there are areas with a high concentration or density of labeled antibody, the label will be densely packed, and the fluorescence at these areas can be confirmed. Thus, with the test kit 50, a positive result can be determined if both the test line and the control line are visible, and a negative result can be determined if only the control line is visible. The test line and control line can be visually confirmed when colored particles or gold colloid particles are used, and can be confirmed by a fluorescence detector such as a fluorescence scanner when fluorescent beads are used.
[0075] Fluorescence can be detected by a fluorescence detector, such as a fluorescence scanner. With a fluorescence scanner, excitation light is shone onto an analytical carrier 1 supporting the analyte, and the fluorescence of fluorescent beads excited by the excitation light can be detected.
[0076] The test kit 50 can be used for, for example, infectious disease testing; genetic analysis; pregnancy testing; livestock testing; allergen testing for food, animals, plants, metals, house dust, etc.
[0077] The analytes for test kit 50 include, for example, amino acids, peptides, proteins, genes, sugars, lipids, cells, or complexes thereof. More specifically, the analytes include peptides such as PCT (procalcitonin); proteins such as urinary albumin; hormones such as hCG (human chorionic gonadotropin) and LH (luteinizing hormone); HBs antigen, rotavirus antigen, adenovirus antigen, and RSV (Respiratory Antigens or antibodies for viral infections such as syncytial virus antigen, influenza virus antigen, norovirus antigen, mumps virus antigen, cytomegalovirus antigen, herpes simplex virus antigen, varicella-zoster virus antigen, SARS (severe acute respiratory syndrome) antigen, HBs antibody, HCV (hepatitis C virus) antibody, HIV antibody, EBV antibody, RSV antibody, rubella virus antibody, measles virus antibody, enterovirus antibody, dengue virus antibody, and SARS antibody; antigens or antibodies for bacterial infections such as pneumococcal antigen, mycoplasma antigen, group A streptococcus antigen, Legionella antigen, Mycobacterium tuberculosis antigen, Neisseria gonorrhoeae antigen, tetanus antigen, mycoplasma antibody, Helicobacter pylori antibody, and Mycobacterium tuberculosis antibody; antigens or antibodies for chlamydia infections such as chlamydia antigen; antigens or antibodies for spirochete infections such as Treponema pallidum antibody; and antigens or antibodies for protozoan diseases such as malaria antibody and toxoplasma antibody.
[0078] In addition, the analytical carrier 1 can be used as, for example, a separation membrane for gases or liquids; a hygroscopic material; a water-absorbing material; an adsorbent material for adsorbing foreign substances such as pollen, particulate matter, bacteria, odor components, and heavy metals; a wiping sheet; a test sheet for chemicals such as concentrated sulfuric acid, for urine testing, and for pH testing; a disinfectant and sterilizing material; a reflective material: a standard white plate; a separator for batteries and electric double-layer capacitors; a catalyst carrier; a reaction field for synthesis reactions, etc.; and a heat insulating material. Examples of the separation membranes mentioned above include reverse osmosis membranes, ion exchange membranes, and gas separation membranes. Examples of the adsorbent materials mentioned above include masks, filtration membranes, and filters.
[0079] [4. Method for manufacturing analytical carriers] Next, the method for manufacturing the analytical carrier 1 according to this embodiment will be described. As shown in Figure 3, the method for manufacturing the analytical carrier 1 according to this embodiment includes a sintering step S1, an anodizing step S2, a melting step S3, a lamination step S4, and a peeling step S5. The method for manufacturing the analytical carrier 1 may also include a hydration step as needed. Each step will be described in detail below.
[0080] <Sintering process S1> The sintering step S1 is a step of sintering a plurality of aluminum metal particles 113 on an aluminum substrate 105. Through this step, as shown in Figure 4, a sintered material 100 can be obtained comprising an aluminum substrate 105 and a sintered body 110 laminated on the aluminum substrate 105 and having aluminum metal particles 113 sintered thereon. In Figure 4, a sintered body 110 is shown as an example in which aluminum metal particles 113 are sintered on one side of the aluminum substrate 105, but it is sufficient to sinter the aluminum metal particles 113 on at least one side of the aluminum substrate 105, or to sinter the aluminum metal particles 113 on both sides of the aluminum substrate 105. In other words, the sintered body 110 may have aluminum metal particles 113 on one side of the aluminum substrate 105, or it may have aluminum metal particles 113 on both sides of the aluminum substrate 105.
[0081] The aluminum metal particles 113 contain at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys. Hereafter, at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys will also be simply referred to as aluminum.
[0082] The aluminum content of high-purity aluminum may be 99.95% by mass or more, 99.99% by mass or more, or 99.995% by mass or more. The aluminum content of pure aluminum may be 99.00% by mass or more, 99.50% by mass or more, or 99.80% by mass or more. The aluminum content of pure aluminum is less than 99.95% by mass. High-purity aluminum and pure aluminum may contain elements other than aluminum (Al). The elements other than aluminum contained in pure aluminum may include one or more of the following elements: silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B), zirconium (Zr), etc. Pure aluminum may be an A1000 series alloy as defined in JIS H4000.
[0083] Aluminum alloys contain aluminum and elements other than aluminum. The elements other than aluminum in an aluminum alloy may include one or more of the following elements: silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B), zirconium (Zr), etc. The total content of elements other than aluminum in an aluminum alloy may exceed 1% by mass. The total content of elements other than aluminum in an aluminum alloy may be 10% by mass or less, or 5% by mass or less. The content of each element other than aluminum in an aluminum alloy may be 10% by mass or less, or 1% by mass or less. The aluminum alloy may be any of the 1000 series, 2000 series, 3000 series, 4000 series, 5000 series, 6000 series, 7000 series, or 8000 series alloys specified in JIS H4000.
[0084] The average particle size of the multiple aluminum metal particles 113 is 0.1 μm or more and 20 μm or less. By setting the average particle size of the aluminum metal particles 113 to 0.1 μm or more, the strength of the porous body 10 is improved, and damage during transport can be suppressed. By setting the average particle size of the aluminum metal particles 113 to 20 μm or less, the flow rate of the analytical carrier 1 can be improved. The average particle size of the aluminum metal particles 113 may be 1 μm or more, 3 μm or more, or 5 μm or more. The average particle size of the aluminum metal particles 113 may be 18 μm or less, 15 μm or less, or 10 μm or less. The average particle size of the multiple aluminum metal particles 113 before sintering is the D50 value obtained by measuring the particle size distribution on a volume basis using laser diffraction. The shape of the particles is not particularly limited and may be spherical, polygonal, irregularly shaped, flaky, or fibrous.
[0085] Multiple aluminum metal particles 113 can be manufactured by known methods. Multiple aluminum metal particles 113 can be manufactured by, for example, atomization, melt spinning, rotating disk method, rotating electrode method, or other rapid solidification methods. Among these, from the viewpoint of industrial productivity, multiple aluminum metal particles 113 are preferably manufactured by atomization, and more preferably by gas atomization. Specifically, multiple aluminum metal particles 113 are preferably manufactured by atomizing molten metal.
[0086] The aluminum substrate 105 contains at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys. For high-purity aluminum, pure aluminum, and aluminum alloys, those described in the section on aluminum metal particles 113 can be used. The composition of aluminum contained in the aluminum metal particles 113 and the composition of aluminum contained in the aluminum substrate 105 may be the same or different.
[0087] The thickness of the aluminum substrate 105 is greater than 0 μm. Depending on the application, the thickness of the aluminum substrate 105 may be 10 μm or more, or 20 μm or more. For example, the thickness of the aluminum substrate 105 may be 1 mm or less, 100 μm or less, 10 μm or less, or 1 μm or less.
[0088] Multiple aluminum metal particles 113 may be sintered after being placed on at least one surface of the aluminum substrate 105. At least one surface of the aluminum substrate 105 may be covered with aluminum powder containing the multiple aluminum metal particles 113, a compact obtained by compacting the aluminum powder, or a liquid composition such as a slurry containing the multiple aluminum metal particles 113. The liquid composition may be applied to the surface of the aluminum substrate 105 by known methods such as spray painting, brush painting, roller painting, air knife painting, bar coating, spin coating, dipping, or screen printing. The liquid composition should be applied to achieve the desired thickness of the porous body 10, taking its composition into consideration.
[0089] The surface of the aluminum substrate 105 may be pre-treated before placing the multiple aluminum metal particles 113 onto its surface. The pre-treatment may include a step of roughening the surface of the aluminum substrate 105. The pre-treatment is not particularly limited and may include washing, etching, or blasting.
[0090] The aluminum powder or composition may contain, as needed, a pore-forming agent, a binder, a sintering aid, a surfactant, and a solvent, in addition to a plurality of aluminum metal particles 113. Known substances can be used for these.
[0091] The content of aluminum metal particles 113 in the composition is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 31% by mass or more. The content of aluminum metal particles 113 in the composition is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 57% by mass or less.
[0092] The pore-forming material is a material that promotes the formation of voids 12 within the sintered body 110. The pore-forming material may be, for example, particles containing a polymer material. It is preferable that the pore-forming material has low solubility in the solvent described later. The polymer material may contain polysaccharides or resins. The polysaccharides may contain, for example, starch. The resins may contain polyolefins such as polyethylene or polypropylene.
[0093] The average particle size of the pore-forming material is preferably 0.1 μm or more and 20 μm or less. By setting the average particle size of the pore-forming material to 0.1 μm or more, the above average pore diameter can be easily set to 0.1 μm or more. By setting the average particle size of the pore-forming material to 20 μm or less, the above average pore diameter can be easily set to 20 μm or less. The average particle size of the pore-forming material may be 0.5 μm or more, or 1 μm or more. Also, the average particle size of the pore-forming material may be 10 μm or less, or 8 μm or less. The average particle size of the pore-forming material is the D50 value obtained by measuring the particle size distribution on a volume basis using the laser diffraction method.
[0094] The content of the pore-forming material in the composition may be 5% by mass or more, 10% by mass or more, or 12% by mass or more. The content of the pore-forming material in the composition may be 30% by mass or less, 25% by mass or less, or 23% by mass or less. When the content of the pore-forming material is above the lower limit of the above range, the formation of voids 12 in the sintered body 110 is promoted, and the packing rate of the sintered body 110 decreases, making it easier to obtain a sintered body 110 with a desired packing rate and a porous body 10 with a desired porosity. Furthermore, when the content of the pore-forming material is below the upper limit of the above range, it is easier to prevent an excessive decrease in the packing rate of the sintered body 110 and to suppress a decrease in the strength of the porous body 10.
[0095] The binder is preferably highly soluble in the solvent described later. The binder may include, for example, synthetic resins such as carboxy-modified polyolefin resin, vinyl acetate resin, vinyl chloride resin, vinyl chloride-vinyl acetate copolymer resin, vinyl alcohol resin, butyral resin, vinyl fluoride resin, acrylic resin, polyester resin, urethane resin, epoxy resin, urea resin, phenol resin, acrylonitrile resin, nitrocellulose resin, paraffin wax, or polyethylene wax, or natural resins such as wax, tar, animal glue, lacquer, pine resin, or beeswax. The binder content in the composition may be 0.5% by mass or more, or 1% by mass or more. The binder content in the composition may be 30% by mass or less, or 20% by mass or less.
[0096] The solvent may include organic solvents such as water, ethanol, toluene, ketones, or esters. To volatilize the solvent, the laminate on which the composition has been applied to the aluminum substrate 105 may be dried at a temperature of 20°C to 300°C for 1 to 30 minutes, if necessary.
[0097] The sintering temperature is not particularly limited, but is preferably between 560°C and 660°C. Setting the sintering temperature to 560°C or higher can improve the strength of the porous body 10. Setting the sintering temperature to 660°C or lower can suppress the melting of multiple aluminum metal particles 113. The sintering temperature may be 570°C or higher, or 580°C or higher. Furthermore, the sintering temperature may be 650°C or lower, or 620°C or lower.
[0098] The sintering time depends on the sintering temperature and other factors, but may be, for example, 5 to 24 hours. The sintering atmosphere is not particularly limited and may be any of the following: a vacuum atmosphere, an inert gas atmosphere, an oxidizing gas atmosphere (atmosphere), or a reducing gas atmosphere. Among these, a vacuum atmosphere or a reducing gas atmosphere is preferred. Furthermore, the sintering conditions may be atmospheric pressure, reduced pressure, or increased pressure.
[0099] If the above composition contains a pore-forming material, it is preferable to heat the composition at a temperature of 200°C to 500°C before sintering. Heating the composition at 200°C or higher allows the pore-forming material to burn slowly, forming more uniformly dispersed voids 12 within the sintered body 110. Heating the composition at 500°C or lower suppresses oxidation of the surface of the aluminum metal particles 113 during heating, thereby improving the strength of the porous body 10. The heating temperature may be 250°C or higher, or 280°C or higher. The heating temperature may be 460°C or lower, or 430°C or lower.
[0100] The heating time is preferably 5 hours or more and 20 hours or less. By heating for 5 hours or more, more uniformly dispersed voids 12 can be formed within the sintered body 110. By heating for 20 hours or less, the sintering of each aluminum metal particle 113 is prevented, and more uniformly dispersed voids 12 can be formed within the sintered body 110. The heating time may be 7 hours or more, or 15 hours or less. The sintering atmosphere may be a vacuum atmosphere, an inert gas atmosphere, or an oxidizing gas atmosphere. The sintering conditions may be atmospheric pressure, reduced pressure, or increased pressure.
[0101] The sintering step S1 may include a first sintering layer formation step for obtaining a first sintered layer and a second sintering layer formation step for obtaining a second sintered layer. In the first sintering layer formation step, a plurality of aluminum metal particles 113 are sintered to obtain a first sintered layer. The plurality of aluminum metal particles 113 may be sintered after being arranged on at least one surface of the aluminum substrate 105, as described above. In the second sintering layer formation step, a laminate in which the plurality of aluminum metal particles 113 are arranged on the surface of the first sintered layer may be sintered. The first sintering layer formation step and the second sintering layer formation step may differ in at least one of the following: the average particle diameter, aspect ratio, constituent material, composition, type of pore-forming material, or average particle diameter of the plurality of aluminum metal particles 113 used.
[0102] The packing density of the sintered body 110 is 10% by volume to 60% by volume. By setting the packing density of the sintered body 110 to 10% by volume or more, it becomes easier to obtain a porous body 10 in which the porosity is below the upper limit of the desired range after the anodizing process S2 and the melting process S3. This suppresses the peeling of aluminum metal particles 113 from the porous body 10 and improves the strength of the porous body 10. Furthermore, by setting the packing density of the sintered body 110 to 60% by volume or less, it becomes easier to obtain a porous body 10 in which the porosity is above the lower limit of the desired range after the anodizing process S2 and the melting process S3. This improves the suction performance of the porous body 10. The packing density may be 15% by volume or more, or 20% by volume or more. Furthermore, the packing density may be 55% by volume or less, or 50% by volume or less. The filling rate can be obtained by subtracting the mass of the aluminum substrate 105 from the total mass of the sintered material 100, as described in the Examples section below, and then dividing the mass of the sintered body 110 obtained by subtracting the mass of the aluminum substrate 105 by the mass of the sintered body 110 assuming a filling rate of 100%.
[0103] <Hydration process> The method for manufacturing the analytical carrier 1 according to this embodiment may include a hydration treatment step before the anodizing step S2. The hydration treatment step is a step to efficiently form an anodic oxide film by forming a hydration film on the surface of the aluminum metal particles 113, thereby converting the hydration film into an oxide film during the subsequent anodizing treatment in the anodizing step S2. The hydration treatment step also has the effect of lifting and cleaning dirt and other contaminants present on the aluminum surface before anodizing, and can suppress the occurrence of unevenness in appearance when an anodic oxide film is applied afterward. The hydration treatment step is a step of heat-treating the sintered material 100 with hot water such as boiling water. The hot water may be pure water, or it may be an aqueous phosphoric acid solution in which phosphoric acid is dissolved. The concentration of the aqueous phosphoric acid solution may be, for example, 0.001 mL / L to 5 mL / L. An aqueous phosphoric acid solution of this concentration can be obtained, for example, by preparing an 85% by mass aqueous phosphoric acid solution with pure water to the desired concentration. Adding phosphoric acid enhances the surface cleaning effect. When the sintered body 110 is subjected to hydration treatment, a hydration film of aluminum hydroxide is formed on the surface of the aluminum, and as described above, the outer shell 14 may contain the hydration film, although the outer shell 14 may contain the hydration film.
[0104] <Anodizing process S2> As shown in Figure 5, the anodic oxidation process S2 is a process of anodizing the sintered material 100 to form an outer shell 14 including an anodic oxide film on the surface of the aluminum metal particles 113. Alternatively, in the anodic oxidation process S2, coating layers 17, 117 including an anodic oxide film containing aluminum oxide may be formed on the surface of the aluminum substrate 105 on which the aluminum metal particles 113 are laminated. In the anodic oxidation process S2, for example, the anode on which the sintered material 100 is placed and the cathode on which stainless steel (SUS) is placed are immersed in an electrolyte and subjected to electrolytic treatment.
[0105] The electrolyte used in the anodic oxidation process S2 may contain at least one selected from the group consisting of citric acid, boric acid, phosphoric acid, sulfuric acid, oxalic acid, and salts thereof. By anodic oxidation with an electrolyte containing citric acid, boric acid, phosphoric acid, or salts thereof, a barrier-type anodic oxide film can be formed. When forming a barrier-type anodic oxide film, compared to the porous type, an anodic oxide film of a constant thickness can be easily formed by controlling the voltage. By anodic oxidation with an electrolyte containing sulfuric acid, oxalic acid, phosphoric acid, or salts thereof, a porous-type anodic oxide film can be formed. When forming a porous-type anodic oxide film, the anodic oxide film can be formed at a lower voltage compared to the barrier type, thus reducing electricity costs. Examples of salts include ammonium salts, sodium salts, potassium salts, and silicates. From the viewpoint of availability, it is preferable that the salt contains at least one of ammonium salts and sodium salts.
[0106] The conditions for anodizing are not particularly limited. For example, the electrolysis temperature may be 0°C or higher, 10°C or higher, 20°C or higher, 30°C or higher, 40°C or higher, or 50°C or higher. The electrolysis temperature may be 70°C or lower, 60°C or lower, or 50°C or lower. The electrolysis voltage varies depending on the type of electrolyte, but may be 0.1V or higher, or 1V or higher. Also, the electrolysis voltage varies depending on the type of electrolyte, but may be 500V or lower, or 400V or lower. Furthermore, the electrolysis time may be 0.1 minutes or more, or 1 minute or more. The electrolysis time may be 60 minutes or less, or 20 minutes or less. Anodizing may be carried out in a single step, or it may be carried out in multiple different steps.
[0107] <Dissolution process S3> As shown in Figure 6, the melting step S3 is a step in which the aluminum metal particles 113 surrounded by the outer shell 14 are melted. In the melting step S3, for example, the sintered material 100, in which the outer shell 14 was formed in the anodizing step S2, can be immersed in a melting solution. In the melting step S3, the high-purity aluminum, pure aluminum, and aluminum alloy contained in the aluminum metal particles 113 are melted inside the outer shell 14 and dissolved to the outside of the outer shell 14. As a result, a cavity 15 is created inside the outer shell 14. Consequently, the outer shell 14 remains as a shell-like structure, forming hollow particles 13. That is, hollow aluminum particles are formed, including the outer shell 14 and the cavity 15 surrounded by the outer shell 14. In the sintered body 110, a continuous series of outer shells 14 are formed on the outer surfaces of multiple adjacent aluminum metal particles 113. Therefore, the anodic oxidation process S2 leaves the outer shell 14 derived from multiple aluminum metal particles 113 in a continuous form, while the dissolution process S3 dissolves the inside of the aluminum metal particles 113, forming multiple cavities 15 that connect and form a continuous structure inside the outer shell 14. As a result, a skeleton 11 is formed by the aggregation of multiple hollow particles 13.
[0108] The dissolving solution used to dissolve the aluminum metal particles 113 in dissolution step S3 may contain at least one acid selected from the group consisting of phosphoric acid, sulfuric acid, nitric acid, and salts thereof, or at least one alkali selected from the group consisting of sodium hydroxide and potassium hydroxide. Such a dissolving solution has excellent solubility for aluminum metal particles 113. The dissolving solution preferably contains, for example, phosphoric acid. The salts contained in the aqueous solution may contain at least one metal salt selected from the group consisting of aluminum, sodium, magnesium, calcium, and zinc.
[0109] When phosphoric acid is used as the dissolving solution, the concentration of phosphoric acid may be, for example, 0.1 g / L to 1000 g / L. The dissolution temperature in dissolution step S3 may be, for example, 50°C to 80°C. The dissolution time in dissolution step S3 may be 1 minute to 60 minutes.
[0110] In the method for manufacturing the analytical carrier 1, a metal member (aluminum member) 120 is formed by laminating a porous body 10 onto an aluminum substrate 105 by performing the anodic oxidation step S2 and the dissolution step S3 once each or by repeating them. By performing the anodic oxidation step S2 and the dissolution step S3 once each or by repeating them, hollow particles 13 can be formed having an outer shell 14 containing an anodic oxidation film containing aluminum oxide and a cavity 15 surrounded by the outer shell 14. When the anodic oxidation step S2 and the dissolution step S3 are performed once each, in the peeling step S5, the aluminum metal particles 113 surrounded by the outer shell 14 are dissolved, and the aluminum substrate 105 is also dissolved, allowing the aluminum substrate 105 to be peeled off from the laminate 130, thus simplifying the manufacturing process and improving productivity. Figure 6 illustrates a metal member 120 in which a porous body 10 is formed on one side of an aluminum substrate 105. However, it is sufficient to form the porous body 10 on at least one side of the aluminum substrate 105, or the porous body 10 may be formed on both sides of the aluminum substrate 105. In other words, the metal member 120 may have the porous body 10 laminated on one side of the aluminum substrate 105, or the porous body 10 may be formed on both sides of the aluminum substrate 105.
[0111] In the method for manufacturing the analytical carrier 1, the anodizing step S2 and the dissolution step S3 are repeated alternately, and the number of repetitions of the anodizing step S2 and the dissolution step S3 may be between 2 and 20. The number of repetitions of the anodizing step S2 and the dissolution step S3 is not particularly limited as it is affected by the voltage conditions of the anodizing step S2 and the processing time of the dissolution step S3. However, by setting the number of repetitions to 2 or more, the amount of metallic aluminum remaining in the hollow particles 13 can be reduced, and the light transmittance of the porous body 10 can be improved. This makes it possible to provide an analytical carrier 1 with high visibility. Also, even if the number of repetitions exceeds 20, the amount of metallic aluminum remaining does not decrease further, so by setting the number of repetitions to 20 or less, work efficiency can be improved. The number of repetitions may be, for example, 2 or more, 3 or more, 5 or more, or 8 or more. The number of repetitions of the anodizing step S2 and the dissolution step S3 may be 15 or less, or 10 or less.
[0112] In the melting process S3, the high-purity aluminum, pure aluminum, and aluminum alloy contained in the aluminum substrate 105 are dissolved inside the aluminum substrate 105 and eluted to the outside of the aluminum substrate 105. This creates space inside the aluminum substrate 105 due to the elution. Here, the melting in the melting process S3 proceeds from the aluminum metal particles 113, and proceeds to the areas where the aluminum substrate 105 and the aluminum metal particles 113 are sintered and where high-purity aluminum, pure aluminum, and aluminum alloy are present. For this reason, melting proceeds more easily on the side with the coating layer 17, which is on the same side as the porous body 10 and covers the inner surface of the aluminum substrate 105 while communicating with the porous body 10 side via the communication holes 18, than on the side with the coating layer 117, which is on the opposite side of the porous body 10 and covers the entire outer surface of the aluminum substrate 105. In this way, as the dissolution of the porous body 10 progresses, the aluminum substrate 105 on the same side as the porous body 10 near the boundary between the aluminum substrate 105 and the coating layer 17 dissolves and a portion remains, creating a state where the aluminum substrate 105 on the opposite side of the porous body 10 and the coating layer 17 are connected. If the dissolution progresses too much, the aluminum substrate 105 and the coating layer 17 will peel off before the subsequent lamination process S4, reducing handling and making it difficult to create the analytical carrier 1 in which the porous body 10 is supported on the support 20. On the other hand, if the dissolution progresses too little, it will be difficult to separate the porous body 10 from the aluminum substrate 105 in the subsequent peeling process S5. For this reason, it is preferable to continue dissolution until the porous body 10 side of the aluminum substrate 105 and the coating layer 17 are partially connected.
[0113] When the anodizing process S2 and the dissolution process S3 are performed once each, in the dissolution process S3, aluminum metal particles may be dissolved such that the percentage of the mass difference (amount dissolved) obtained by subtracting the mass of the metal member 120 after the dissolution process S3 from the mass of the sintered material 100 after the anodizing process S2 is 10% or more and 40% or less relative to the mass of the sintered material 100 after the sintering process S1. For example, in the dissolution process S3, aluminum metal particles 113 may be dissolved such that the mass of aluminum metal dissolved in the dissolution process S3 is 10% or more and 40% or less relative to the mass of the sintered material 100 obtained in the sintering process S1. In this way, it is possible to suppress the peeling of the aluminum substrate 105 and the coating layer 17 before the lamination process S4, and to further suppress the separation of the porous body 10 from the aluminum substrate 105 in the peeling process S5.
[0114] <Lamination process S4> As shown in Figure 7, the lamination step S4 is a step in which the porous body 10 of the metal member 120 is bonded to the support 20 to form a laminate 130 in which the aluminum substrate 105, the porous body 10, and the support 20 are laminated in this order. In the lamination step S4, the adhesive layer 22 is bonded to the outer shell 14. By bonding the porous body 10 to the support 20, the support 20 can support the porous body 10. Furthermore, because the aluminum substrate 105, the porous body 10, and the support 20 are laminated in this order, the aluminum substrate 105 can be easily peeled off in the peeling step S5 described later. In Figure 7, a laminate 130 is illustrated in which the support 20 is bonded to the porous body 10 formed on one side of the aluminum substrate 105, but it is sufficient to bond the support 20 to at least one side of the aluminum substrate 105, or the support 20 may be bonded to both sides of the aluminum substrate 105. In other words, the metal member 120 may have a support 20 laminated on a porous body 10 formed on one side of an aluminum substrate 105, or the support 20 may be laminated on porous bodies 10 formed on both sides of the aluminum substrate 105.
[0115] When the support 20, before the porous body 10 is bonded, is placed on a white reflective standard calibrated by the measuring instrument, the surface on the support 20 to which the porous body 10 is bonded is measured with the measuring instrument, and L * a * b * L in color systems * The value may be 75 or higher. * By setting the value to 75 or higher, the discriminability during water absorption can be improved. * The value may be 80 or greater, 85 or greater, 90 or greater, or 95 or greater.
[0116] As described above, the support 20 may include a support layer 21 and an adhesive layer 22. The porous body 10 and the support layer 21 may be bonded together with an adhesive. The adhesive may form the adhesive layer 22 by curing. The adhesive may be at least one selected from the group consisting of solvent-volatilizing adhesives, moisture-curing adhesives, heat-curing adhesives, curing agent-mixed adhesives, anaerobic-curing adhesives, UV-curing adhesives, hot-melt adhesives, pressure-sensitive adhesives, and re-wet adhesives. The adhesive may, for example, contain an ethylene vinyl acetate copolymer and bond the porous body 10 and the support layer 21 by heat melting.
[0117] For example, a single layer of thermoplastic resin may be used as the support 20, and the porous body 10 may be bonded to the support 20 by applying heat to one side of the support 20 and melting it. Alternatively, the support 20 may be formed by not providing a support layer 21 on the support 20, and instead applying and curing an adhesive directly onto the porous body 10 to form a support 20 consisting of an adhesive layer 22. The following describes the first to fourth lamination methods according to the configuration of the support 20.
[0118] As shown in Figure 8, the first lamination method can be applied when the support 20a is pre-laminated and integrated with a support layer 21a made of thermoplastic resin and an adhesive layer 22a made of thermoplastic resin having a softening temperature lower than the softening temperature of the support layer 21a. Such a support 20a is commercially available as a laminate film. In the first lamination method, the support 20a, 20a are superimposed on the metal member 120 with the adhesive layers 22a, 22a facing each other and the support layer 21a facing outwards. With the support 20a superimposed, heat is applied to the support 20a from both outer sides where the support layers 21a, 21a are positioned, such that the adhesive layer 22a softens but the support layer 21a does not, thereby softening the adhesive layer 22a and bonding the adhesive layer 22a to the metal member 120. As a result, the metal member 120 and the adhesive layer 22a are bonded on both sides of the metal member 120, and a support layer 21a is provided on the outside of the adhesive layer 22a, thereby forming a laminate 130a in which the support layer 21a, adhesive layer 22a, metal member 120, adhesive layer 22a, and support layer 21a are stacked in this order. When applying heat to the adhesive layer 22a to perform bonding, it is preferable to sandwich the stacked metal member 120 and support 20a,20a between at least one pair of rollers, and move the metal member 120 and support 20a,20a by rotating the rollers while applying heat and pressure to the metal member 120 and support 20a,20a.
[0119] As shown in Figure 9, the second lamination method can be applied when the support 20b is formed by bonding an adhesive layer 22b made of thermoplastic resin to a support layer 21b that can be bonded to the adhesive layer 22b. In the second lamination method, the adhesive layer 22b, 22b and the support layer 21b, 21b are stacked on both outer sides of the metal member 120 in this order. With the layers stacked, heat is applied from both outer sides where the support layers 21b, 21b are located, to soften the adhesive layer 22b, thereby bonding the adhesive layer 22b to the metal member 120 and the support layer 21b. As a result, the support 20b is formed by bonding and integrating the adhesive layer 22b and the support layer 21b, and the metal member 120 and the support layer 21b are bonded via the adhesive layer 22b. Furthermore, by bonding the metal member 120 to the adhesive layer 22b on both sides of the metal member 120, and providing a support layer 21b on the outside of the adhesive layer 22b, a laminate 130b can be formed in which the support layer 21b, adhesive layer 22b, metal member 120, adhesive layer 22b, and support layer 21b are stacked in this order. When applying heat to the adhesive layer 22b to perform bonding, it is preferable to sandwich the stacked metal member 120, adhesive layers 22b, 22b, and support layers 21b, 21b between at least one pair of rollers, and rotate the rollers to move the metal member 120, adhesive layers 22b, 22b, and support layers 21b, 21b while applying heat and pressure to them.
[0120] The third lamination method can be applied when the support 20c consists only of an adhesive layer 22c made of thermoplastic resin. In the third lamination method, the adhesive layers 22c, 22c and the release body 25 are layered on both outer sides of the metal member 120 in this order. As the release body 25, a sheet-like material that does not soften when heated and does not adhere to the adhesive layers 22c, 22c, but can transfer heat to the adhesive layers 22c is preferably used. For example, a sheet made of paper (release paper) can be used as the release body 25. By applying enough heat to soften the adhesive layer 22 from both outer sides where the release bodies 25, 25 are placed while the layers are layered, the adhesive layer 22 is softened, and the adhesive layer 22 and the metal member 120 can be bonded in the same way as in the first and second lamination methods. After bonding, as shown in Figure 10, the release body 25 is peeled off the adhesive layer 22. As a result, the metal member 120 and the adhesive layer 22 are bonded together on both sides of the metal member 120, forming a laminate 130c in which the adhesive layer 22, the metal member 120, and the adhesive layer 22 are stacked in this order. When applying heat to the adhesive layer 22 to perform bonding, it is preferable to sandwich the stacked metal member 120, adhesive layers 22, 22, and release body 25 between at least one pair of rollers, and rotate the rollers to move the metal member 120, adhesive layers 22, 22, and release body 25 while applying heat and pressure to them.
[0121] The fourth lamination method can be applied when the support 20d is formed by bonding an adhesive layer 22d made of an adhesive (tack) to a support layer 21d that can be bonded to the adhesive layer 22d. As shown in Figure 11, in the fourth lamination method, first, adhesive is applied to one side of each of the support layers 21d, 21d to form the adhesive layers 22d, 22d. Next, the support layers 21d, 21d with the adhesive layers 22d, 22d formed on them are overlapped on both outer sides of the metal member 120, with the adhesive layer 22d, 22d side facing the metal member 120. With the layers overlapped, a force sufficient to bond the adhesive layer 22d to the metal member 120 and the support layer 21d is applied from both outer sides where the support layers 21d, 21d are positioned, thereby bonding the adhesive layer 22d to the metal member 120 and the support layer 21d. As a result, the adhesive layer 22d and the support layer 21d are bonded together to form a support body 20d, and the metal member 120 and the support layer 21d are bonded together via the adhesive layer 22d. Furthermore, the metal member 120 and the adhesive layer 22d are bonded together on both sides of the metal member 120, and the support layer 21d is provided on the outside of the adhesive layer 22d, thereby forming a laminate 130d in which the support layer 21d, adhesive layer 22d, metal member 120, adhesive layer 22d, and support layer 21d are stacked in this order. When applying force to the adhesive layer 22d to perform bonding, it is preferable to sandwich the overlapping metal members 120, adhesive layers 22d, 22d, and support layers 21d, 21d between at least one pair of rollers, and rotate the rollers to move the metal members 120, adhesive layers 22d, 22d, and support layers 21d, 21d while applying pressure to them.
[0122] <Peeling process S5> As shown in Figure 12, the peeling step S5 is a step in which the aluminum substrate 105 is dissolved and peeled off from the laminate 130 to form the analytical support 1. By peeling off the aluminum substrate 105 from the laminate 130, the porous body 10 can be made visible. In Figure 12, the laminate 130 from which the aluminum substrate 105 and the coating layer 117 have been peeled off is shown as an example, but the analytical support 1 only needs to be formed from at least one side of the laminate 130 by peeling off the aluminum substrate 105, or the analytical support 1 may be formed from both sides of the laminate 130. That is, the laminate 130 subjected to the peeling step S5 may have the support 20 laminated on a porous body 10 formed on one side of the aluminum substrate 105, or the support 20 may be laminated on a porous body 10 formed on both sides of the aluminum substrate 105.
[0123] If the anodic oxidation step S2 and the dissolution step S3 are performed once each, the peeling step S5 may dissolve the aluminum metal particles 113 surrounded by the outer shell 14, as well as the aluminum substrate 105, and peel off the aluminum substrate 105 from the laminate 130 to form the analytical carrier 1. In the peeling step S5, all of the aluminum metal particles 113 contained in the porous body 10 may be dissolved. In this specification, "all of the aluminum metal particles 113" means substantially all of the aluminum metal particles 113 are dissolved. Specifically, this means that the content of aluminum metal particles 113 contained in the porous body 10 after the peeling step S5 is 10% by mass or less. The content of aluminum metal particles 113 contained in the porous body 10 after the peeling step S5 may be 5% by mass or less, 1% by mass or less, or 0% by mass.
[0124] In the peeling step S5, the aluminum substrate 105 may be dissolved using a peeling solution. In the peeling step S5, 10% or more by mass of the aluminum substrate 105, 20% or more by mass, 30% or more by mass, 40% or more by mass, 50% or more by mass, 60% or more by mass, 70% or more by mass, 80% or more by mass, or 90% or more by mass may be dissolved.
[0125] In the peeling step S5, the aluminum substrate 105 may be dissolved with an acidic or alkaline solution to separate the coating layer 117 formed on the side of the aluminum substrate 105 opposite to the porous body 10 from the porous body 10. This makes it possible to manufacture an analytical carrier 1 comprising the porous body 10 including the coating layer 17 and the support 20. Alternatively, the aluminum substrate 105 may be dissolved and the coating layer 117 may be naturally peeled off from the porous body 10. Alternatively, the aluminum substrate 105 may be partially dissolved and forcibly peeled off from the laminate 130 by manual or mechanical means. Alternatively, the aluminum substrate 105 may be peeled off from the laminate 130 by manual or mechanical means without dissolving the aluminum substrate 105 after the lamination step S4.
[0126] The stripping solution used in the stripping step S5 may contain at least one alkali selected from the group consisting of sodium hydroxide and potassium hydroxide. Stripping solutions containing these alkalis have low viscosity and can easily penetrate deep into the inside of the porous body 10. Therefore, by using such a stripping solution, the stripping of the aluminum substrate 105 can be promoted. The stripping solution may be an aqueous solution, for example, an aqueous solution containing sodium hydroxide.
[0127] The stripping solution used in stripping step S5 may contain at least one organic acid selected from the group consisting of citric acid and gluconic acid. Stripping solutions containing these organic acids can form complexes with dissolved aluminum in the stripping solution. Therefore, by using these stripping solutions, the precipitation of aluminum can be suppressed and the stability of the stripping solution can be improved. The stripping solution may also contain the alkali and organic acid mentioned above. For example, the stripping solution may contain sodium hydroxide and citric acid.
[0128] The stripping solution used in stripping step S5 may contain at least one acid selected from the group consisting of phosphoric acid, sulfuric acid, and nitric acid. Stripping solutions containing these acids can also strip the aluminum substrate 105. The stripping solution may contain, for example, phosphoric acid, or it may contain both phosphoric acid and sulfuric acid.
[0129] The temperature of the peeling solution in peeling step S5 may be between 30°C and 70°C. By setting the temperature of the peeling solution to 30°C or higher, the peeling of the aluminum substrate 105 can be accelerated, and the time required for peeling step S5 can be shortened. By setting the temperature of the peeling solution to 70°C or lower, the excessive generation of bubbles can be suppressed. This makes it possible to suppress damage to the porous body 10 in peeling step S5.
[0130] The processing time in the peeling process S5 is not particularly limited and may be 1 minute or more. The processing time may be 1 hour or more, 2 hours or more, or 4 hours or more. There is no particular upper limit to the processing time, but from the viewpoint of work efficiency, it may be, for example, 24 hours or less. The processing time may be 15 hours or less, 10 hours or less, or 6 hours or less.
[0131] In the peeling step S5, the aluminum substrate 105 may be peeled off in a single step using only one type of peeling solution. Alternatively, the peeling step S5 may involve peeling off the aluminum substrate 105 in multiple steps. When peeling off the aluminum substrate 105 in multiple steps, the same type of peeling solution may be used in each step, or different types of peeling solutions may be used. When peeling off the aluminum substrate 105 in multiple steps, the peeling conditions, such as peeling temperature and peeling time, may be the same in each step, or they may be different. Furthermore, after treating the aluminum substrate 105 with the peeling solution, treatments such as neutralization with a solution containing phosphoric acid, washing with water, and drying may be carried out.
[0132] <Effects and Effects> As described above, the method for manufacturing the analytical carrier 1 according to this embodiment is a method for manufacturing the analytical carrier 1 comprising a porous body 10 and a support 20 including an adhesive layer 22 that supports the porous body 10 on one surface and adheres to the porous body 10. The porous body 10 includes a skeleton 11 formed by the aggregation of a plurality of hollow particles 13 and a plurality of voids 12 surrounded by the skeleton 11. The hollow particles 13 have an outer shell 14 including an anodic oxide film containing aluminum oxide and a cavity 15 surrounded by the outer shell 14. The skeleton 11 is formed by the continuous arrangement of the outer shells 14 of a plurality of hollow particles 13. The manufacturing method includes a sintering step S1 in which a plurality of aluminum metal particles 113 are sintered on an aluminum substrate 105 to obtain a sintered material 100 comprising an aluminum substrate 105 and a sintered body 110 laminated on the aluminum substrate 105 and in which the aluminum metal particles 113 are sintered. The manufacturing method includes an anodizing step S2 in which a sintered material 100 is anodized to form an outer shell 14 containing an anodic oxide film on the surface of aluminum metal particles 113. The manufacturing method includes a melting step S3 in which the aluminum metal particles 113 surrounded by the outer shell 14 are melted. In the above manufacturing method, a metal member 120 is formed in which a porous body 10 is laminated on an aluminum substrate 105 by performing the anodizing step S2 and the melting step S3 once each or by repeating them. The above manufacturing method includes a lamination step S4 in which the porous body 10 of the metal member 120 is bonded to a support 20, and the adhesive layer 22 is bonded to the outer shell 14, thereby forming a laminate 130 in which the aluminum substrate 105, the porous body 10, and the support 20 are laminated in this order. At this time, in the lamination step S4, the porous body 10 is bonded to the adhesive layer 22 to form a laminate 130 in which the aluminum substrate 105, the porous body 10, and the adhesive layer 22 are laminated in this order. The above manufacturing method includes a peeling step S5 in which the aluminum substrate 105 is melted and peeled off from the laminate 130. The aluminum metal particles 113 contain at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys. The aluminum substrate 105 contains at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys.The average particle size of the multiple aluminum metal particles 113 is between 0.1 μm and 20 μm. The packing density of the sintered body 110 is between 10 volume% and 60 volume%. The support 20 contains a resin or elastomer that is resistant to organic solvents. According to this manufacturing method, the analytical support 1 described above can be produced. [Examples]
[0133] The embodiment will be described in more detail below with reference to examples and comparative examples, but the embodiment is not limited to these.
[0134] [Example 1] (Slurry preparation) First, a slurry was prepared by uniformly dispersing 24 parts by mass of aluminum metal particles, 26 parts by mass of pore-forming material, and 1 part by mass of binder in 49 parts by mass of solvent. The aluminum metal particles (AHZL58FN, manufactured by Toyo Aluminum Co., Ltd.) were pure aluminum (JIS A1080) with a purity of 99.80% by mass or higher. The aluminum metal particles were approximately spherical, with an average particle diameter of 3 μm. As the pore-forming material, starch (Nikka Carica® AS-500S, manufactured by Nikka Ltd.) with an average particle diameter of 7 μm was used. An ethyl cellulose resin was used as the binder. Butyl acetate was used as the solvent.
[0135] (sintering) A slurry was applied to one side of an aluminum substrate (aluminum base material) having a thickness of 30 μm using a comma coater (registered trademark) of Hirano Techseed Co., Ltd., so that the thickness of the sintered body would be 50 μm. The slurry was dried at 100°C for 1.5 minutes, then heated at 350°C for 5 hours in an air atmosphere, and further sintered at 620°C to 640°C for 10 hours in an argon gas atmosphere. In this way, a sintered material was produced with a sintered body provided on the aluminum substrate.
[0136] Next, the sintered material was washed with a 5 g / L oxalic acid aqueous solution at 50°C for 10 minutes, and then washed with pure water at room temperature (30°C) for 1 minute.
[0137] (First anodic oxidation) The sintered material was subjected to first anodizing to form an outer shell containing aluminum oxide on the surface of the aluminum metal particles. Specifically, the sintered material placed at the anode and the stainless steel (SUS) placed at the cathode were immersed in electrolyte A at 50°C, which was prepared with pure water to contain 1 g / L of 98% citric acid and 0.1 g / L of 95% triammonium citrate. Then, a current of 50 mA / cm was applied until the voltage reached 450 V. 2 The material was then subjected to anodizing treatment by running it through a flowing stream and maintaining a voltage of 450V for 3 minutes. The first anodized sintered material was washed with pure water for 0.5 minutes.
[0138] (First dissolution treatment) The first anodized sintered material underwent a first dissolution treatment by immersing it in an aqueous solution prepared by diluting an 85% phosphoric acid solution with pure water to a concentration of 500 mL / L (718 g / L) at 70°C for 3 minutes to further dissolve the aluminum metal. The sintered material after the first dissolution treatment was washed with pure water for 1 minute.
[0139] (Drying treatment) The aluminum component according to this example was fabricated by drying the sintered material that underwent the first melting treatment at 200°C for 5 minutes.
[0140] (Lamination process) The lamination process was carried out using the following lamination method. Using a transparent laminate film as a support, the aluminum component prepared as described above was laminated with the laminate film on both sides, creating a laminate with laminate film laminated on both sides of the aluminum component. Fellowes laminate film (PET / LDPE / EVA, 100 μm thick, GLOSS) was used as the laminate film. A 40 μm thick EVA film was used as the adhesive layer, and a 60 μm thick PET / LDPE film was used as the support layer. A Fellowes Proteus A3 laminator was used, and the aluminum component was laminated to the laminate film at a lamination speed of approximately 1.4 cm / s to achieve a lamination temperature of 90°C. The laminate with the aluminum component laminated to the laminate film was cut to a width of 25 mm. The lamination method corresponds to the first lamination method described above.
[0141] (Peeling treatment) The peeling process was carried out according to the following peeling condition 1.
[0142] (Peeling condition 1) The 25 mm wide laminate obtained as described above was immersed in an aqueous solution prepared with pure water to contain 200 g / L of sodium hydroxide at 40°C for 600 minutes. This treatment peeled off and removed the aluminum substrate from the laminate. Then, it was neutralized by immersing it in an aqueous solution prepared with pure water to contain 40 mL / L of 85% phosphoric acid aqueous solution at 70°C for 5 minutes.
[0143] (Drying treatment) The laminate from which the aluminum substrate had been removed was washed with pure water for 1 minute and dried at 50°C for 10 minutes to prepare the analytical support material for this example.
[0144] [Example 2] An analytical support was prepared in the same manner as in Example 1, except that a support consisting of a 40 μm thick OPP layer as the support layer and a 30 μm thick LDPE layer as the adhesive layer was laminated, and the lamination temperature was set to 120°C.
[0145] [Example 3] An analytical support was prepared in the same manner as in Example 1, except that the first dissolution treatment time was set to 5 minutes and a support was used consisting of a 40 μm thick OPP layer as the support layer and a 25 μm thick acrylic adhesive layer as the bonding layer.
[0146] [Comparative Example 1] Cytiva's nitrocellulose membrane FF120HP, which consists of nitrocellulose formed on a 100 μm thick PET film, was used as the analytical support.
[0147] [evaluation] The following evaluations were performed on the analytical carriers for each example. These results are shown in Tables 1 to 5.
[0148] (Filling rate) The packing density of the sintered body was obtained by measuring the sintered material before hydration treatment using the following procedure. • Projection area of 100 cm from sintered material 2 A sample was cut out for measurement. Measurements and calculations were then performed on the sample. (In this specification, the projected area refers to the horizontal projected area of the sintered material or sintered body when viewed from above in the same direction as the thickness direction.) The total mass Ma(g) of the sintered material, including the sintered body and the aluminum substrate, was measured. The total thickness Wa (cm) of the sintered body was measured using a micrometer. The thickness Wb (cm) of the aluminum substrate was measured using a micrometer. The mass Mb (g) of the aluminum substrate was calculated using the formula: Mb = density of aluminum substrate × Wb × 100. In this example, the density of the aluminum substrate and sintered body portion, both made of aluminum, is 2.7 g / cm³. 3 I calculated it using this method. The mass Mc(g) of the sintered body portion was determined using the formula Mc = Ma - Mb. The mass Md (g) of the sintered body portion, assuming a 100% filling rate, was calculated using the formula: Md = density of the sintered body material × (Wa - Wb) × projected area of the sintered body portion = 2.7 × (Wa - Wb) × 100. The packing density of the sintered body contained in the measurement sample was determined using the formula: packing density (%) = (Mc / Md) × 100.
[0149] (Porosity of porous materials) The porosity of the porous material was obtained by dividing the cumulative pore volume of the porous material by the volume of the porous material. The cumulative pore volume of the porous material was obtained by integrating the pore volumes of pores having a diameter of 0.1 μm or more and 100 μm or less, which were measured by the mercury intrusion method.
[0150] (Cross-sectional observation) The analytical support was frozen by immersion in liquid nitrogen, then the frozen analytical support was bent and fractured, and platinum was deposited on the fracture surface to achieve a platinum film thickness of approximately 5 nm, thereby obtaining a sample for cross-sectional observation. A cross-sectional observation image (cross-sectional SEM image) was obtained by observing the cross-section of this observation sample in a plane perpendicular to the adhesive interface between the porous material and the adhesive layer using a scanning electron microscope (ULTRAplus) manufactured by Carl Zeiss Corporation.
[0151] (Thickness of the outer shell) The thickness of the outer shell was measured from cross-sectional SEM images obtained by observing using the cross-sectional observation method described above. The thickness of the outer shell was obtained by measuring the thickness of 10 hollow particles and calculating the average value.
[0152] (Thickness of the adhesive layer) The thickness of the adhesive layer was measured from the cross-sectional SEM images obtained by observing using the cross-sectional observation method described above. Within a 50 μm width range parallel to the adhesive interface between the porous material and the adhesive layer, the thickness of the adhesive layer was measured at the position where the thickness in the thickness direction of the material constituting the adhesive layer was greatest. The thickness of the adhesive layer was obtained by measuring the thickness of the adhesive layer at five points in five different ranges and calculating the average value.
[0153] (Thickness of the adhesive area) The thickness of the adhesive portion was measured from the cross-sectional SEM image obtained by observing using the cross-sectional observation method described above. Within a 50 μm width range parallel to the adhesive interface between the porous material and the adhesive layer, a line was drawn passing through the part of the porous material closest to the adhesive layer (bottommost) and parallel to the direction of the adhesive interface between the porous material and the adhesive layer, and a line was drawn passing through the part of the adhesive layer closest to the porous material (topmost) and parallel to the direction of the adhesive interface between the porous material 10 and the adhesive layer 22. The distance between these two lines was measured as the thickness of the adhesive portion 23. The thickness of the adhesive portion was obtained by measuring the thickness of the adhesive portion at five points in five different ranges and calculating the average value.
[0154] (Cumulative surface area of pores in porous materials) The cumulative pore surface area of the porous material was obtained by converting the pore volume of pores with a diameter of 0.1 μm to 100 μm, obtained by the mercury intrusion method, into a surface area for each pore diameter and then summing them up.
[0155] (Average pore size of porous material (4V / A)) The average pore size (4V / A) of the porous material was calculated using the following formula. Average pore diameter of a porous material = 4 × (cumulative pore volume of the porous material) / (cumulative pore surface area of the porous material) The cumulative pore volume and cumulative pore surface area of the porous material were obtained as described above.
[0156] (Combined pore surface area ratio) The ratio of the cumulative surface area of pores with a diameter of 0.1 μm to less than 1 μm to the cumulative surface area of pores with a diameter of 1 μm to 10 μm was calculated. The cumulative surface area of pores with a diameter of 1 μm to 10 μm was obtained by summing the surface areas of pores with a diameter of 1 μm to 10 μm. Similarly, the cumulative surface area of pores with a diameter of 0.1 μm to less than 1 μm was obtained by summing the surface areas of pores with a diameter of 0.1 μm to less than 1 μm. The cumulative surface area of the porous material was determined by the mercury intrusion method as described above.
[0157] (The ratio of metallic aluminum to the components constituting a porous material containing aluminum element) The metallic aluminum content in the porous material containing aluminum elements was measured as follows, and the ratio of metallic aluminum to the components constituting the porous material containing aluminum elements was calculated. 1. The porous portion of the analytical support was scraped off using a stainless steel spatula. 2. 2.0 g was weighed out from the scraped-off sample. 3. For the weighed samples, the metallic aluminum content (mass%) relative to the components constituting the porous material containing aluminum was measured according to the ICP emission spectrometry method for decomposition and separation of metallic aluminum as specified in JIS G2404:2022. 4. Using the following formula, the ratio of metallic aluminum to the components constituting the porous material containing aluminum was calculated from the metallic aluminum content (mass%) to the components constituting the porous material containing aluminum. The ratio of metallic aluminum to the components constituting the porous material containing aluminum element. = (Metallic aluminum content in the components constituting the porous material containing aluminum element) / (100 - (Metallic aluminum content in the components constituting the porous material containing aluminum element))
[0158] (Arithmetic mean roughness Sa) The arithmetic mean roughness Sa of the porous surface of the analytical carrier according to Example 1 was measured in accordance with ISO 25178. The arithmetic mean roughness Sa was measured using a Bruker AXS 3D white-light interference microscope ContourGT-I under the conditions of a measurement range of 60 μm × 79 μm, objective lens 115x, and internal lens 1x. For the analytical carrier of Example 1, the surface of the porous side supported by the support of the analytical carrier was observed. For each sample, a 60 μm × 60 μm image was acquired and the surface roughness Sa (μm) was calculated. The surface roughness Sa was obtained by calculating the average value of the numerical values of a total of 5 fields of view.
[0159] (Bending test) As shown in Figure 13, holes 210 with a diameter of 1 mm were made 5 mm from both ends of an analytical carrier 1 cut to 10 mm x 100 mm. A nylon thread 220 with a diameter of 0.165 mm was passed through the holes 210, and 10 g E-2 class weights 230 were attached to each end of the analytical carrier 1. The analytical carrier 1 was placed on a stainless steel rod 240 with a diameter of 2 mm and a length of 5 cm, so that the porous body of the analytical carrier 1 was in contact with the stainless steel rod 240 at the longitudinal center of the analytical carrier 1. As shown in Figure 14, the stainless steel rod 240 was slowly lifted until the weights 230 at both ends of the analytical carrier 1 were lifted off the ground, held for 10 seconds, and then the stainless steel rod 240 was returned to its original position. After that, the surface of the porous body 10 was visually observed and evaluated. If no wrinkles remained on the surface of the porous material and no peeling occurred, it was rated "Excellent." If wrinkles remained but no peeling occurred, it was rated "Acceptable." If wrinkles remained and peeling occurred, it was rated "Unacceptable." Wrinkles were considered to have remained if they were visible to the naked eye and were on the order of millimeters or larger. Furthermore, if the porous material 10 and the support 20 separated within the plane of the analytical carrier 1, and the minimum width of the separated portion was 2 mm or more and the maximum length was 5 mm or more, it was considered that peeling of the porous material 10 had occurred.
[0160] (Amount dissolved) The amount of dissolved material was calculated by measuring Ma, Mb, and Mc on the sintered material after sintering using the following procedure, and then determining the amount based on Ma, Mb, and Mc. Before measuring each mass, the material was dried at 50°C for 30 minutes. • Projection area of 100 cm from sintered material 2 A sample was cut out for measurement. Measurements and calculations were then performed on the sample. The total mass Ma(g) of the sintered material, including the sintered body and the aluminum substrate, was measured. The total mass Mb(g) of the sintered material, including the sintered body after anodizing and the aluminum substrate, was measured. The total mass Mc(g) of the sintered material, including the sintered body after melting and the aluminum substrate, was measured. Dissolution amount (%)=(Mb-Mc)×100 / Ma In Example 1, Ma = 1.71 g, Mb = 1.64 g, and Mc = 1.40 g, resulting in a solubility of 14%.
[0161] (Suction test) Methanol (99.8% by mass), ethanol (99.5% by mass), acetone (99.0% by mass), or deionized water (liquid 310) was placed in glass beakers 320 as shown in Figure 15, with the liquid level reaching 5 mm. The analytical carrier 1, cut to 5 mm x 50 mm, was placed upright in the beaker 320 so that the angle between the carrier and the liquid surface was 110 degrees, and the lid 330 was placed over it. The time required for the liquid in beaker 320 to be drawn up to a height of 4 cm from the liquid surface was recorded as the first measurement. Subsequently, the analytical carrier 1 was removed from beaker 320, dried at 50°C for 15 minutes, and after drying, the analytical carrier 1 was placed upright again in the glass beaker 320 and the lid was placed over it in the same manner as above. The time required for the liquid 310 in beaker 320 to be drawn up to a height of 4 cm from the liquid surface was recorded as the second measurement. Solvent resistance was judged to be acceptable if the difference between the first and second test times was within ±50%. However, if analytical carrier 1 was unable to draw up the liquid to a depth of 4 cm even after 30 minutes, the test was stopped, and it was determined that analytical carrier 1 lacked solvent resistance due to the dissolution of the porous material.
[0162] [Table 1]
[0163] [Table 2]
[0164] [Table 3]
[0165] [Table 4]
[0166] [Table 5]
[0167] [Consider] As shown in Tables 2 to 5, in the analytical carriers of Examples 1 to 3, since aluminum oxide was used as the porous material, there was no significant difference in the absorption time between the first and second absorptions when methanol, ethanol, acetone, and deionized water were absorbed. On the other hand, in the analytical carrier of the comparative example, since nitrocellulose was used as the porous material, the porous material dissolved when methanol, ethanol, and acetone were absorbed.
[0168] Next, the materials shown in Table 6 were immersed in methanol (99.8% by mass), ethanol (99.5% by mass), or acetone (99.0% by mass) for 5 minutes, and the change in mass of the materials before and after immersion was measured.
[0169] [Table 6]
[0170] None of the materials listed in Table 6 dissolved in methanol, ethanol, or acetone, and their mass change rate was less than 10%. Furthermore, polyethylene terephthalate, polypropylene (OPP), polypropylene (CPP), polyethylene, polyamide, and phenol showed a mass change rate of less than 0.5% in methanol, ethanol, and acetone. Ethylene vinyl acetate copolymer showed a mass change rate of less than 5% in methanol, ethanol, and acetone. Acrylic adhesive showed a mass change rate of less than 5% in methanol and ethanol, and a mass change rate of less than 10% in acetone. These results indicate that polyethylene terephthalate, polypropylene (OPP), polypropylene (CPP), polyethylene, polyamide, and phenol have even higher organic solvent resistance than ethylene vinyl acetate copolymer and acrylic adhesive.
[0171] Although this embodiment has been described above with reference to examples and comparative examples, this embodiment is not limited to these, and various modifications are possible within the scope of the gist of this embodiment. [Explanation of symbols]
[0172] 1. Analytical carrier 10 Porous material 11 Skeleton 12 void 13 Hollow particles 14 Outer shell 15 Cavity 17 Covering layer 18 Communication hole 20 Support 21 Support layer 22 Adhesive layer 23 Adhesive part 24 Auxiliary part 100 Sintered material 105 Aluminum base material 110 Sintered body 113 Aluminum metal particles 117 Covering layer 120 Metal components 130 Laminate S1 Sintering process S2 Anodizing process S3 Melting process S4 Lamination process S5 Peeling process
Claims
1. An analytical carrier comprising a porous body and a support that supports the porous body on one side, The porous body includes a framework formed by the aggregation of a plurality of hollow particles, and a plurality of voids surrounded by the framework. The hollow particle has an outer shell containing an anodic oxide film containing aluminum oxide, and a cavity surrounded by the outer shell. The aforementioned skeleton is formed by the continuous arrangement of the outer shells of the plurality of hollow particles. The porosity of the porous material is 50% by volume or more and less than 100% by volume. The average pore size of the porous material is 0.1 μm or more and 20 μm or less. The support includes an adhesive layer that adheres to the porous body, The adhesive layer is bonded to the outer shell. The support comprises an analytical carrier having resistance to organic solvents, such as a resin or elastomer.
2. The analytical carrier according to claim 1, wherein the resin or elastomer having resistance to organic solvents exhibits a weight loss of less than 10% before and after immersion in an immersion test in methanol, ethanol, and acetone, respectively, followed by standing at room temperature for 5 minutes and then drying at 50°C for 10 minutes.
3. The support may be polyethylene, polypropylene, polyolefin, ethylene vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyamide, polyester, (meth)acrylic resin, epoxy resin, urethane resin, fluororesin, styrene resin, ABS resin, silicone resin, phenolic resin, melamine resin, polyvinyl alcohol, polycyanoacrylate, isocyanate adhesive, urethane resin adhesive, urethane resin solvent adhesive, urethane resin emulsion adhesive, acrylic resin adhesive, acrylic resin anaerobic adhesive, olefin adhesive, silicone adhesive, rubber adhesive, ethylene vinyl acetate resin emulsion adhesive, The analytical carrier according to claim 1 or 2, comprising at least one selected from the group consisting of epoxy resin adhesives, epoxy resin emulsion adhesives, vinyl chloride resin solvent adhesives, chloroprene rubber adhesives, cyanoacrylate adhesives, aqueous polymer-isocyanate adhesives, styrene-butadiene rubber solution adhesives, styrene-butadiene rubber latex adhesives, nitrile rubber adhesives, nitrocellulose adhesives, phenol resin adhesives, modified silicone adhesives, polyimide adhesives, polystyrene resin solvent adhesives, polybenzimidazole adhesives, polymethacrylate resin solution adhesives, and light- and ultraviolet-curing resin adhesives.
4. The support comprises the adhesive layer and a support layer that supports the adhesive layer. The analytical carrier according to claim 1 or 2, wherein the adhesive layer is interposed between the porous body and the support layer.
5. The analytical carrier according to claim 4, wherein the support layer comprises at least one selected from the group consisting of a resin or elastomer having organic solvent resistance, a metal, and paper.
6. The analytical carrier according to claim 4, wherein the support layer comprises at least one selected from the group consisting of polyester, acrylic resin, urethane resin, silicone resin, epoxy resin, polyolefin, cellulose resin, styrene resin, polyimide, and polycarbonate.
7. The analytical carrier according to claim 1, wherein the adhesive layer comprises the resin or elastomer having resistance to organic solvents.
8. A method for manufacturing an analytical carrier comprising a porous body and a support that includes an adhesive layer that supports the porous body on one side and adheres to the porous body, The porous body includes a framework formed by the aggregation of a plurality of hollow particles, and a plurality of voids surrounded by the framework. The hollow particle has an outer shell containing an anodic oxide film containing aluminum oxide, and a cavity surrounded by the outer shell. The aforementioned skeleton is formed by the continuous arrangement of the outer shells of the plurality of hollow particles. The aforementioned manufacturing method is A sintering step to obtain a sintered material comprising: sintering multiple aluminum metal particles on an aluminum substrate; the aluminum substrate; and a sintered body laminated on the aluminum substrate and in which the aluminum metal particles are sintered; An anodizing step of anodizing the sintered material to form the outer shell including the anodic oxide film on the surface of the aluminum metal particles, A dissolution step of dissolving the aluminum metal particles surrounded by the outer shell, Includes, In the above manufacturing method, the anodizing step and the dissolution step are performed once each or repeated to form a metal member in which the porous body is laminated on the aluminum substrate. The aforementioned manufacturing method is A lamination step in which the porous body of the metal member is bonded to the support, and the adhesive layer is bonded to the outer shell, thereby forming a laminate in which the aluminum substrate, the porous body, and the support are laminated in this order. A peeling step of dissolving the aluminum substrate and peeling the aluminum substrate from the laminate, Includes, The aluminum metal particles contain at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys. The aluminum substrate contains at least one type of aluminum selected from the group consisting of high-purity aluminum, pure aluminum, and aluminum alloys. The average particle diameter of the plurality of aluminum metal particles is 0.1 μm or more and 20 μm or less. The filling density of the sintered body is 10% by volume or more and 60% by volume or less. A method for producing an analytical carrier, wherein the support comprises a resin or elastomer resistant to organic solvents.
Citation Information
Patent Citations
Developing solvent for immuno-chromatography, measuring method and kit
JP2003344406A